Polishing composition, wetting agent for semiconductor, water-soluble polymer, and manufacturing method of them
By using the treated water-soluble polymer in the polishing composition, the problem of insufficient surface polishing quality of semiconductor chips in the prior art is solved, and a lower number of surface defects and better filtration performance is achieved.
Patent Information
- Application Number
- JP2024229660
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-22
Smart Images

Figure 2025066105000006 
Figure 2025066105000007 
Figure 2025066105000008
Abstract
Description
[Technical field]
[0001] The present invention relates to a polishing composition, a wetting agent for semiconductors, a water-soluble polymer, and methods for producing the same. [Background technology]
[0002] Water-soluble polymers are used in various applications such as dispersants, thickeners, emulsion polymerization stabilizers, protective colloids, paints, cosmetics, water retention agents, pharmaceutical preparations, and grinding aids. Among these, hydroxyethyl cellulose, a semi-synthetic polymer compound, is particularly excellent in properties such as dispersibility and thickening. Hydroxyethyl cellulose is used in addition to abrasive grains and water as a grinding aid to improve the protection and wettability of the substrate surface in the rinsing process and polishing process of various substrates such as semiconductor substrates represented by silicon wafers.
[0003] Patent Document 1 discloses a method for producing dried hydrophobic hydroxyethyl cellulose, which is useful as a polishing aid that can improve the polishing rate in combination with abrasive grains. Specifically, Patent Document 1 discloses that synthesized undried hydrophobic hydroxyethyl cellulose is dried and then pulverized to obtain dried hydrophobic hydroxyethyl cellulose. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-104781 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, with the development of technology, there is an increasing demand for higher quality surface conditions for objects to be polished, such as semiconductor substrates, semiconductor elements, and silicon wafers.
[0006] Therefore, an object of the present invention is to provide a polishing composition, a wetting agent for semiconductors, a water-soluble polymer, and methods for producing these, which are capable of achieving a good surface condition of a substrate. [Means for solving the problem]
[0007] The above object of the present invention can be achieved by the following means: A polishing composition comprising an abrasive grain and a water-soluble polymer, The water-soluble polymer is A step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution; and a step of applying pressure to the solutions by colliding the solutions with each other.
[0008] A method for producing a polishing composition containing an abrasive grain and a water-soluble polymer, comprising the steps of: A step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution; applying pressure to the solutions by colliding them with each other; mixing abrasive particles into the solution under pressure; A method for producing a polishing composition comprising the steps of:
[0009] The above object of the present invention can also be achieved by the following means: A wetting agent for a semiconductor, comprising a water-soluble polymer, The water-soluble polymer is A step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution; applying pressure to the solutions by colliding them with each other; A wetting agent for semiconductors, which is a water-soluble polymer treated by a method comprising the steps of:
[0010] A method for producing a wetting agent for a semiconductor, comprising: A step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution; applying pressure to the solutions by colliding them with each other; A method for producing a wetting agent for semiconductors, comprising:
[0011] Furthermore, the above object of the present invention can also be achieved by the following means: A step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution; applying pressure to the solutions by colliding them with each other; A water-soluble polymer for use as a polishing composition and / or a semiconductor wetting agent, the polymer being treated by a method comprising the steps of:
[0012] A step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution; applying pressure to the solutions by colliding them with each other; A method for producing a water-soluble polymer for use as a polishing composition and / or a semiconductor wetting agent, comprising the steps of: Effect of the Invention
[0013] According to the present invention, a polishing composition, a wetting agent for semiconductors, and a water-soluble polymer are provided that can achieve a good surface condition of a substrate. More specifically, by polishing and / or rinsing with the polishing composition and / or the wetting agent for semiconductors according to the present invention, the number of defects observed on the substrate can be further reduced. In particular, it is effective in reducing defects such as LPD-N (Light Point Defect Non-cleanable) and LPD (Light Point Defect).
[0014] In addition, according to the present invention, it is possible to selectively remove high molecular weight substances of water-soluble polymers used in the manufacture of a polishing composition and / or a wetting agent for semiconductors. This selective removal of high molecular weight substances can improve the filterability of a solution containing a water-soluble polymer, a polishing composition and / or a wetting agent for semiconductors. Furthermore, it is possible to selectively remove high molecular weight substances without increasing the amount of impurities contained in the water-soluble polymer and the solution containing the same. [Brief description of the drawings]
[0015] [Figure 1]FIG. 1 shows GPC elution curves of the starting water-soluble polymer and the treated water-soluble polymer in the example where HEC1 was used as the starting water-soluble polymer. [Diagram 2] FIG. 2 shows GPC elution curves of the raw water-soluble polymer and the treated water-soluble polymer in the example where HEC2 was used as the raw water-soluble polymer. [Diagram 3] FIG. 3 shows differential molecular weight distribution curves of the raw water-soluble polymer and the treated water-soluble polymer in the example where HEC1 was used as the raw water-soluble polymer. [Figure 4] FIG. 4 shows differential molecular weight distribution curves of the raw water-soluble polymer and the treated water-soluble polymer when HEC2 was used as the raw water-soluble polymer in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, the embodiments of the present invention will be described. Note that the present invention is not limited to only the following embodiments. In addition, in this specification, the range "X to Y" means "X or more and Y or less". Furthermore, unless otherwise specified, the operation and measurement of physical properties are performed under the conditions of room temperature (range of 20°C to 25°C) and relative humidity of 40% RH to 50% RH.
[0017] The mechanism by which the present invention can solve the above problems has not been completely clarified, but the present inventors speculate in part as follows.
[0018] In the present invention, by applying pressure to a solution containing the raw water-soluble polymer, the entanglement of the high molecular weight components of the raw water-soluble polymer is eliminated and the molecular chains of the high molecular weight components of the raw water-soluble polymer are cleaved. As a result, the high molecular weight components of the raw water-soluble polymer are removed, the viscosity is reduced compared to that of the raw water-soluble polymer before treatment, and the filterability of the solution containing the obtained water-soluble polymer (also simply referred to as the "water-soluble polymer to be treated" in this specification), the polishing composition and / or the semiconductor wetting agent is improved.
[0019] In addition, the method of applying pressure to the solution containing the raw water-soluble polymer involves colliding solutions containing the raw water-soluble polymer with each other to apply pressure to the solution, and since collision with other components is not used, the incorporation of impurities is unlikely to occur.
[0020] As a result, it is possible to remove high molecular weight substances that cause surface defects from the raw water-soluble polymer, and also to prevent an increase in impurities due to the treatment of the raw water-soluble polymer. As a result, it is considered that the number of surface defects (e.g., LPD-N and LPD) of a substrate can be further reduced when polished and / or rinsed with the polishing composition and / or semiconductor wetting agent according to the present invention.
[0021] The mechanism by which high molecular weight substances are selectively removed has not been completely clarified, but the present inventors speculate in part as follows.
[0022] That is, in the collision step, the high molecular weight components in the raw water-soluble polymer collide more frequently than the low molecular weight components, and the high molecular weight components contain a greater proportion of points at which molecular chains break than the low molecular weight components, and therefore it is believed that the high molecular weight components are selectively removed.
[0023] The above mechanism is based on speculation, and whether it is correct or not does not affect the technical scope of the present invention.
[0024] The present invention will be described in detail below, but the present invention is not limited to the following description.
[0025] <Polishing composition, wetting agent for semiconductors, and methods for producing the same> One aspect of the present invention relates to a polishing composition comprising an abrasive grain and a water-soluble polymer, the water-soluble polymer being a water-soluble polymer that has been treated by a method including a step of dissolving a raw water-soluble polymer in a solvent to prepare a solution (also referred to herein simply as the "dissolution step"), and a step of colliding the solutions with each other and applying pressure to the solutions (also referred to herein simply as the "collision step").
[0026] Another aspect of the present invention relates to a wetting agent for semiconductors, comprising a water-soluble polymer, the water-soluble polymer being treated by a method including a dissolving step and a collision step.
[0027] The treatment of the water-soluble polymer used in the polishing composition and / or the wetting agent for semiconductors of the present application will be described below.
[0028] <Treatment of water-soluble polymer and treated water-soluble polymer> One aspect of the present invention relates to a method for treating a water-soluble polymer used in a polishing composition and / or a wetting agent for semiconductors, the method comprising the steps of dissolving a raw water-soluble polymer in a solvent to prepare a solution (dissolving step) and colliding the solutions with each other and applying pressure to the solution (collision step). Another aspect of the present invention relates to a water-soluble polymer for use in a polishing composition and / or a wetting agent for semiconductors, treated by a method comprising the dissolving step and the collision step.
[0029] [Dissolution process] The water-soluble polymer of the present invention is a water-soluble polymer that has been treated by a method that includes a step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution (dissolving step).
[0030] In this specification, "dissolve" means to dissolve or disperse. It is preferable that "dissolve" means to make at least a part of the substance dissolved, and in this case, the remaining part may be dispersed in the solvent, but it is particularly preferable that the substance is completely dissolved.
[0031] (Raw material water-soluble polymer) The type of the water-soluble polymer used as the raw material of the present invention is not particularly limited as long as it is a polymer compound having water solubility. For example, the polymer compound may include those containing a hydroxyl group, a carboxyl group, an acyloxy group, a sulfo group, an amide structure, an imide structure, a quaternary ammonium structure, a heterocyclic structure, a vinyl structure, an ether bond, etc. in the molecule.
[0032] In this specification, "water-soluble" means that the solubility in water (25°C) is 1 g / 100 mL or more, and "polymer compound" means a compound having a weight average molecular weight (Mw) of 2,000 or more. The weight average molecular weight (Mw) can be measured by gel permeation chromatography (GPC), and the details of the measurement method will be described in the Examples.
[0033] As the raw water-soluble polymer, any of natural polymer compounds, semi-synthetic polymer compounds, and synthetic polymer compounds may be used. As the natural polymer compounds, there is no particular limitation, but preferably polysaccharides and the like are included. As the semi-synthetic polymer compounds, there is no particular limitation, but preferably cellulose derivatives, starch derivatives, and the like are included. As the synthetic polymer compounds, there is no particular limitation, but preferably polymers having oxyalkylene units, polymers having structural units derived from vinyl alcohol, polymers having nitrogen atoms, and the like are included. In one embodiment of the present invention, the raw water-soluble polymer contains a hydroxyl group or an ether group from the viewpoint of improving the surface quality. Among them, it is preferable to contain at least one of a polymer having a structural unit derived from vinyl alcohol and a cellulose derivative. The polishing composition and / or semiconductor wetting agent containing these polymers are easy to improve the surface quality after the polishing and / or rinsing process. Specific examples of these compounds are given below.
[0034] The polysaccharides are not particularly limited, but examples thereof include carrageenan and xanthan gum.
[0035] The cellulose derivative is not particularly limited, and examples thereof include cellulose derivatives such as hydroxyethyl cellulose (hereinafter also simply referred to as "HEC"), hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, and carboxymethyl cellulose, as well as pullulan. One type of cellulose derivative may be used alone, or two or more types may be used in combination. Here, the cellulose derivative refers to cellulose in which some of the hydroxyl groups of cellulose are replaced with other substituents.
[0036] The starch derivative is not particularly limited, but examples thereof include cationic starch, starch phosphate, and carboxymethyl starch salts.
[0037] Examples of polymers having oxyalkylene units include, but are not limited to, polyethylene oxide (PEO), polypropylene oxide (PPO), block copolymers of ethylene oxide (EO) and propylene oxide (PO) or butylene oxide (BO), and random copolymers of EO and PO or BO. Among these, block copolymers of EO and PO or random copolymers of EO and PO are preferred. The block copolymers of EO and PO may be diblock copolymers or triblock copolymers containing a PEO block and a polypropylene oxide (PPO) block. Examples of the triblock copolymers include PEO-PPO-PEO type triblock copolymers and PPO-PEO-PPO type triblock copolymers. Among these, PEO-PPO-PEO type triblock copolymers are more preferred.
[0038] In a block or random copolymer of EO and PO, the molar ratio of EO to PO constituting the copolymer [EO / PO] is preferably greater than 1, more preferably equal to or greater than 2, and even more preferably equal to or greater than 3, from the viewpoints of solubility in water, washability, etc. In a more preferred embodiment, the molar ratio [EO / PO] is, for example, equal to or greater than 5.
[0039] The polymer having a structural unit derived from vinyl alcohol may contain only vinyl alcohol units (hereinafter also referred to as "VA units") as repeating units, or may contain repeating units other than VA units (hereinafter also referred to as "non-VA units") in addition to VA units. The type of polymer having a structural unit derived from vinyl alcohol may be used alone or in combination of two or more. The vinyl alcohol unit is a structural portion represented by the following chemical formula: -CH2-CH(OH)-;. The polymer having a structural unit derived from vinyl alcohol may be a random copolymer containing VA units and non-VA units, or may be a block copolymer or a graft copolymer. The polymer having a structural unit derived from vinyl alcohol may contain only one type of non-VA unit, or may contain two or more types of non-VA units.
[0040] The polymer having a structural unit derived from vinyl alcohol used in the raw water-soluble polymer disclosed herein may be unmodified polyvinyl alcohol (unmodified PVA) or modified polyvinyl alcohol (modified PVA). Here, the unmodified PVA refers to a polymer produced by hydrolysis (saponification) of polyvinyl acetate and having a structural unit derived from vinyl alcohol that does not substantially contain repeating units other than repeating units (-CH2-CH(OCOCH3)-) and VA units, which are vinyl polymerized from vinyl acetate. The degree of saponification of the unmodified PVA may be, for example, 60% or more, and from the viewpoint of water solubility, may be 70% or more, 80% or more, or 90% or more. In some embodiments, unmodified PVA having a degree of saponification of 95% or more, or unmodified PVA having a degree of saponification of 98% or more may be preferably used as the raw water-soluble polymer.
[0041] Examples of non-VA units that may be contained in the modified PVA include, but are not limited to, repeating units derived from N-vinyl monomers or N-(meth)acryloyl monomers described below, repeating units derived from ethylene, repeating units derived from alkyl vinyl ethers, and repeating units derived from vinyl esters of monocarboxylic acids having 3 or more carbon atoms. A suitable example of the N-vinyl monomer is N-vinylpyrrolidone. A suitable example of the N-(meth)acryloyl monomer is N-(meth)acryloylmorpholine. The alkyl vinyl ether may be, for example, a vinyl ether having an alkyl group having 1 to 10 carbon atoms, such as propyl vinyl ether, butyl vinyl ether, or 2-ethylhexyl vinyl ether. The vinyl ester of a monocarboxylic acid having 3 or more carbon atoms may be, for example, a vinyl ester of a monocarboxylic acid having 3 to 7 carbon atoms, such as vinyl propanoate, vinyl butanoate, vinyl pentanoate, or vinyl hexanoate.
[0042] The polymer having a structural unit derived from vinyl alcohol may be a modified PVA containing a VA unit and a non-VA unit having at least one structure selected from an oxyalkylene group, a carboxy group, a sulfo group, an amino group, a hydroxyl group, an amide group, an imide group, a nitrile group, an ether group, an ester group, and salts thereof.
[0043] The polymer having a structural unit derived from vinyl alcohol may be a modified PVA in which a part of the VA units contained in the polymer having a structural unit derived from vinyl alcohol is acetalized with an aldehyde compound or a ketone compound. In a preferred embodiment of the technology disclosed herein, the acetalized modified PVA is a polymer obtained by an acetalization reaction between the above-mentioned non-modified PVA and an aldehyde compound.
[0044] In one embodiment of the present invention, the aldehyde compound used to produce the acetalized modified PVA is not particularly limited. In a preferred embodiment, the aldehyde compound has 1 to 7 carbon atoms, more preferably 2 to 7 carbon atoms.
[0045] Examples of the aldehyde compound include formaldehyde; linear or branched alkyl aldehydes such as acetaldehyde, propionaldehyde, n-butylaldehyde, isobutylaldehyde, t-butylaldehyde, and hexylaldehyde; and alicyclic or aromatic aldehydes such as cyclohexanecarbaldehyde and benzaldehyde. These may be used alone or in combination of two or more. In addition, except for formaldehyde, one or more hydrogen atoms may be substituted with halogen or the like. Among them, linear or branched alkyl aldehydes are preferred from the viewpoint of high solubility in water and easy acetalization reaction, and among them, acetaldehyde, n-propylaldehyde, n-butylaldehyde, and n-pentylaldehyde are more preferred.
[0046] As the aldehyde compound, in addition to the above, aldehyde compounds having 8 or more carbon atoms, such as 2-ethylhexylaldehyde, nonylaldehyde, and decylaldehyde, may be used.
[0047] In addition, a cationically modified polyvinyl alcohol having a cationic group such as a quaternary ammonium structure may be used as a polymer having a structural unit derived from vinyl alcohol. Examples of the cationically modified polyvinyl alcohol include those having a cationic group derived from a monomer having a cationic group such as a diallyldialkylammonium salt or an N-(meth)acryloylaminoalkyl-N,N,N-trialkylammonium salt.
[0048] The ratio of the number of moles of VA units to the number of moles of all repeating units constituting a polymer having a structural unit derived from vinyl alcohol may be, for example, 5% or more, 10% or more, 20% or more, or 30% or more. Although not particularly limited, in some embodiments, the ratio of the number of moles of VA units may be 50% or more, 65% or more, 75% or more, 80% or more, or 90% or more (e.g., 95% or more, or 98% or more). Substantially 100% of the repeating units constituting a polymer having a structural unit derived from vinyl alcohol may be VA units. Here, "substantially 100%" means that at least intentionally, a polymer having a structural unit derived from vinyl alcohol does not contain non-VA units, and typically the ratio of the number of moles of non-VA units to the number of moles of all repeating units is less than 2% (e.g., less than 1%), including the case of 0%. In some other embodiments, the ratio of the number of moles of VA units to the number of moles of all repeating units constituting a polymer having a structural unit derived from vinyl alcohol may be, for example, 95% or less, 90% or less, 80% or less, or 70% or less.
[0049] The content of VA units in a polymer having a structural unit derived from vinyl alcohol (content based on mass) may be, for example, 5% by mass or more, 10% by mass or more, 20% by mass or more, or 30% by mass or more. Although not particularly limited, in some embodiments, the content of the VA units may be 50% by mass or more (e.g., more than 50% by mass), 70% by mass or more, or 80% by mass or more (e.g., 90% by mass or more, 95% by mass or more, or 98% by mass or more). Substantially 100% by mass of the repeating units constituting the polymer having a structural unit derived from vinyl alcohol may be VA units. Here, "substantially 100% by mass" means that non-VA units are not included as repeating units constituting the polymer having a structural unit derived from vinyl alcohol, at least intentionally, and typically means that the content of non-VA units in a polymer having a structural unit derived from vinyl alcohol is less than 2% by mass (e.g., less than 1% by mass). In some other embodiments, the content of VA units in a polymer having structural units derived from vinyl alcohol may be, for example, 95% by mass or less, 90% by mass or less, 80% by mass or less, or 70% by mass or less.
[0050] A polymer having a structural unit derived from vinyl alcohol may contain multiple polymer chains with different VA unit contents in the same molecule. Here, the polymer chain refers to a portion (segment) that constitutes a part of a single polymer molecule. For example, a polymer having a structural unit derived from vinyl alcohol may contain a polymer chain A having a VA unit content of more than 50% by mass and a polymer chain B having a VA unit content of less than 50% by mass (i.e., a non-VA unit content of more than 50% by mass) in the same molecule.
[0051] The polymer chain A may contain only VA units as repeat units, or may contain non-VA units in addition to VA units. The content of VA units in the polymer chain A may be 60% by mass or more, 70% by mass or more, 80% by mass or more, or 90% by mass or more. In some embodiments, the content of VA units in the polymer chain A may be 95% by mass or more, or 98% by mass or more. Substantially 100% by mass of the repeat units constituting the polymer chain A may be VA units.
[0052] The polymer chain B may contain only non-VA units as repeat units, or may contain VA units in addition to non-VA units. The content of non-VA units in the polymer chain B may be 60% by weight or more, 70% by weight or more, 80% by weight or more, or 90% by weight or more. In some embodiments, the content of non-VA units in the polymer chain B may be 95% by weight or more, or 98% by weight or more. Substantially 100% by weight of the repeat units constituting the polymer chain B may be non-VA units.
[0053] Examples of polymers having structural units derived from vinyl alcohol that contain polymer chain A and polymer chain B in the same molecule include block copolymers and graft copolymers that contain these polymer chains. The graft copolymers may be graft copolymers having a structure in which polymer chain B (side chain) is grafted to polymer chain A (main chain), or graft copolymers having a structure in which polymer chain A (side chain) is grafted to polymer chain B (main chain). In one embodiment, a polymer having structural units derived from vinyl alcohol and having a structure in which polymer chain B is grafted to polymer chain A can be used.
[0054] Examples of the polymer chain B include a polymer chain having a repeating unit derived from an N-vinyl type monomer as a main repeating unit, a polymer chain having a repeating unit derived from an N-(meth)acryloyl type monomer as a main repeating unit, a polymer chain having an oxyalkylene unit as a main repeating unit, etc. In this specification, the term "main repeating unit" refers to a repeating unit contained in an amount of more than 50% by mass, unless otherwise specified.
[0055] A preferred example of the polymer chain B is a polymer chain having an N-vinyl type monomer as a main repeating unit, i.e., an N-vinyl polymer chain. The content of the repeating unit derived from the N-vinyl type monomer in the N-vinyl polymer chain is typically more than 50% by mass, and may be 70% by mass or more, 85% by mass or more, or 95% by mass or more. Substantially all of the polymer chain B may be a repeating unit derived from an N-vinyl type monomer.
[0056] In this specification, examples of N-vinyl type monomers include monomers having a nitrogen-containing heterocycle (e.g., lactam ring) and N-vinyl chain amides. Specific examples of N-vinyl lactam type monomers include N-vinyl pyrrolidone, N-vinyl piperidone, N-vinyl morpholinone, N-vinyl caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, and the like. Specific examples of N-vinyl chain amides include N-vinyl acetamide, N-vinyl propionic acid amide, N-vinyl butyric acid amide, and the like. The polymer chain B may be, for example, an N-vinyl polymer chain in which more than 50% by mass (e.g., 70% by mass or more, 85% by mass or more, or 95% by mass or more) of its repeating units are N-vinyl pyrrolidone units. Substantially all of the repeating units constituting the polymer chain B may be N-vinyl pyrrolidone units.
[0057] Another example of the polymer chain B is a polymer chain having a repeating unit derived from an N-(meth)acryloyl type monomer as a main repeating unit, i.e., an N-(meth)acryloyl-based polymer chain. The content of the repeating unit derived from an N-(meth)acryloyl type monomer in the N-(meth)acryloyl-based polymer chain is typically more than 50% by mass, and may be 70% by mass or more, 85% by mass or more, or 95% by mass or more. Substantially all of the polymer chain B may be a repeating unit derived from an N-(meth)acryloyl type monomer.
[0058] In this specification, examples of N-(meth)acryloyl type monomers include chain amides having an N-(meth)acryloyl group and cyclic amides having an N-(meth)acryloyl group. Examples of chain amides having an N-(meth)acryloyl group include (meth)acrylamide; N-alkyl(meth)acrylamides such as N-methyl(meth)acrylamide, N-ethyl(meth)acrylamide, N-propyl(meth)acrylamide, N-isopropyl(meth)acrylamide, and Nn-butyl(meth)acrylamide; and N,N-dialkyl(meth)acrylamides such as N,N-dimethyl(meth)acrylamide, N,N-diethyl(meth)acrylamide, N,N-dipropyl(meth)acrylamide, N,N-diisopropyl(meth)acrylamide, and N,N-di(n-butyl)(meth)acrylamide. Examples of cyclic amides having an N-(meth)acryloyl group include N-(meth)acryloylmorpholine and N-(meth)acryloylpyrrolidine.
[0059] Another example of the polymer chain B is a polymer chain containing an oxyalkylene unit as a main repeating unit, i.e., an oxyalkylene-based polymer chain. The content of the oxyalkylene unit in the oxyalkylene-based polymer chain is typically more than 50% by mass, and may be 70% by mass or more, 85% by mass or more, or 95% by mass or more. Substantially all of the repeating units contained in the polymer chain B may be oxyalkylene units.
[0060] Examples of the oxyalkylene unit include an oxyethylene unit, an oxypropylene unit, and an oxybutylene unit. Each of these oxyalkylene units may be a repeating unit derived from the corresponding alkylene oxide. The oxyalkylene unit contained in the oxyalkylene polymer chain may be one type or two or more types. For example, the oxyalkylene polymer chain may contain a combination of an oxyethylene unit and an oxypropylene unit or a butylene oxide unit. In an oxyalkylene polymer chain containing two or more types of oxyalkylene units, the oxyalkylene units may be a random copolymer of the corresponding alkylene oxide, or may be a block copolymer or a graft copolymer. Among them, a block copolymer of an oxyethylene unit and an oxypropylene unit or a random copolymer of an oxyethylene unit and an oxypropylene unit is preferable. The block copolymer of an oxyethylene unit and an oxypropylene unit may be a diblock copolymer, a triblock copolymer, or the like, containing a polyethylene oxide (PEO) block and a polypropylene oxide (PPO) block. Examples of the triblock copolymer include PEO-PPO-PEO type triblock copolymers and PPO-PEO-PPO type triblock copolymers. Usually, PEO-PPO-PEO type triblock copolymers are more preferred.
[0061] Further examples of polymer chain B include polymer chains containing a repeating unit derived from an alkyl vinyl ether (e.g., a vinyl ether having an alkyl group having from 1 to 10 carbon atoms), a polymer chain containing a repeating unit derived from a monocarboxylic acid vinyl ester (e.g., a vinyl ester of a monocarboxylic acid having from 3 or more carbon atoms), a polymer chain in which a part of the VA units has been acetalized with an aldehyde (e.g., an alkyl aldehyde having an alkyl group having from 1 to 7 carbon atoms), and a polymer chain into which a cationic group (e.g., a cationic group having a quaternary ammonium structure) has been introduced.
[0062] As the polymer having a structural unit derived from vinyl alcohol in the raw water-soluble polymer disclosed herein, a non-modified PVA may be used, a modified PVA may be used, or a combination of a non-modified PVA and a modified PVA may be used. In an embodiment in which a non-modified PVA and a modified PVA are used in combination, the amount of modified PVA used relative to the total amount of the polymer having a structural unit derived from vinyl alcohol contained in the raw water-soluble polymer may be, for example, less than 95% by mass, 90% by mass or less, 75% by mass or less, 50% by mass or less, 30% by mass or less, 10% by mass or less, 5% by mass or less, or 1% by mass or less. The raw water-soluble polymer disclosed herein may be preferably implemented, for example, in an embodiment in which only one or more types of non-modified PVA are used as the polymer having a structural unit derived from vinyl alcohol.
[0063] The polymer having a nitrogen atom is not particularly limited, but includes a polymer containing an N-vinyl type monomer unit, an imine derivative, a polymer containing an N-(meth)acryloyl type monomer unit, and the like. For example, poly N-acryloylmorpholine (PACMO), poly N-vinylpyrrolidone (PVP), polyhydroxyethylacrylamide (PHEAA), poly N-vinylimidazole (PVI), poly N-vinylcarbazole, poly N-vinylcaprolactam, poly N-vinylpiperidine, and the like are listed. Among them, from the viewpoint of reducing the haze of the substrate, it is preferable to include poly N-acryloylmorpholine (PACMO). The type of polymer having a nitrogen atom may be used alone or in combination of two or more.
[0064] Among these, from the viewpoint of obtaining a more remarkable effect of improving the filterability of the present invention, semisynthetic polymer compounds or synthetic polymer compounds are preferred, and semisynthetic polymer compounds are more preferred. In one embodiment of the present invention, from the viewpoint of improving the surface quality, the raw material water-soluble polymer preferably contains a hydroxyl group or an ether group, and is more preferably, for example, a cellulose derivative, and further preferably, hydroxyethyl cellulose (HEC).
[0065] The weight average molecular weight (Mw) of the raw water-soluble polymer is not particularly limited as long as it is 2,000 or more as described above. From the viewpoint of the more significant effect of improving the filterability of the present invention, it is preferably 10,000 or more, and more preferably 100,000 or more. From the viewpoint of filterability, the weight average molecular weight (Mw) of the raw water-soluble polymer is preferably 4,000,000 or less, more preferably 3,000,000 or less, even more preferably 2,800,000 or less, and particularly preferably 1,500,000 or less. The dispersity of the raw water-soluble polymer (also represented as "Mw / Mn" in this specification: Mw represents the weight average molecular weight and Mn represents the number average molecular weight) is not particularly limited, but the effect of the present invention tends to be greater as the value is larger. From this viewpoint, the lower limit of Mw / Mn of the raw water-soluble polymer is, for example, preferably more than 5, more preferably 10 or more, even more preferably 15 or more, and even more preferably 20 or more. The upper limit of Mw / Mn of the raw water-soluble polymer is preferably 95 or less, more preferably 90 or more, even more preferably 85 or more, and even more preferably 80 or more. The upper limit of Mw / Mn of the raw water-soluble polymer can be, for example, 75 or less, or 40 or less. The weight average molecular weight (Mw) and number average molecular weight (Mn) can be measured by gel permeation chromatography (GPC), and the details of the measurement method will be described in the Examples.
[0066] According to one embodiment of the present invention, the raw water-soluble polymer is a polymer having a structural unit derived from vinyl alcohol. The weight average molecular weight (Mw) of the polymer having a structural unit derived from vinyl alcohol is preferably 2,000 or more, and more preferably 2,500 or more. More preferably, the molecular weight is 5,000 or more, and even more preferably, 10,000 or more. According to this embodiment, there is a technical effect that the surface quality after the polishing and / or rinsing process is improved. According to one embodiment of the present invention, the weight average molecular weight (Mw) of the polymer having a structural unit derived from polyvinyl alcohol is preferably 500,000 or less, more preferably 300,000 or less, even more preferably 200,000 or less, and even more preferably 150,000 or less. According to this embodiment, the filterability is improved.
[0067] According to one embodiment of the present invention, the raw water-soluble polymer is a cellulose derivative. The weight average molecular weight (Mw) of the cellulose derivative is preferably 2,000 or more, more preferably 10,000 or more, and even more preferably 100,000 or more, for example, 150,000 or more, and may be 200,000 or more. In some aspects, it is preferably 350,000 or more, more preferably 500,000 or more, even more preferably 700,000 or more, and particularly preferably 900,000 or more, for example, 1,250,000 or more. According to such an embodiment, there is a technical effect that the surface quality after the polishing and / or rinsing process is improved. According to one embodiment of the present invention, the weight average molecular weight (Mw) of the cellulose derivative is preferably 4,000,000 or less, more preferably 3,000,000 or less, even more preferably 2,800,000 or less, even more preferably 1,500,000 or less, and particularly preferably 1,000,000 or less, and may be, for example, 750,000 or less, or may be 450,000 or less. According to such an embodiment, the filterability is improved.
[0068] According to one embodiment of the present invention, the raw water-soluble polymer is a polymer having nitrogen atoms. The weight average molecular weight (Mw) of the polymer having nitrogen atoms is preferably 2,000 or more, more preferably 4,000 or more, even more preferably 10,000 or more, and even more preferably 20,000 or more. According to this embodiment, there is a technical effect that the surface quality after the polishing and / or rinsing process is improved. According to one embodiment of the present invention, the weight average molecular weight (Mw) of the raw water-soluble polymer having nitrogen atoms is preferably 1,600,000 or less, more preferably 1,250,000 or less, even more preferably 750,000 or less, and even more preferably 400,000 or less. According to this embodiment, the filterability is improved.
[0069] The weight average molecular weight (Mw), number average molecular weight (Mn) and molecular weight distribution of the water-soluble polymer can be measured by gel permeation chromatography (GPC), specifically, the method described in the Examples is adopted.
[0070] According to one embodiment of the present invention, the content of the raw water-soluble polymer in the dissolving step is preferably 0.5% by mass or more, more preferably 1% by mass or more, and even more preferably 1.5% by mass or more, from the viewpoint of the grinding efficiency in the grinding step. In one embodiment of the present invention, the content of the raw water-soluble polymer in the dissolving step is preferably 5% by mass or less, more preferably 4% by mass or less, and even more preferably 3% by mass or less, from the viewpoint of solubility.
[0071] As the raw material water-soluble polymer according to one embodiment of the present invention, it is preferable to use a powder.
[0072] The raw material water-soluble polymer may be used alone or in combination of two or more kinds, but it is preferable to use one kind alone.
[0073] (solvent) In this specification, the term "solvent" refers to a solvent or a dispersion medium. The solvent is not particularly limited as long as it can dissolve the raw water-soluble polymer, but preferably contains water. The content of water in the solvent is not particularly limited, but is preferably 50% by mass or more, more preferably 90% by mass or more, and even more preferably 100% by mass (water only) relative to the total mass of the solvent. As the water, water containing as few impurities as possible is preferable from the viewpoint of preventing contamination of the substrate and inhibition of the action of other components. For example, water having a total content of transition metal ions of 100 ppb or less is preferable. Here, the purity of the water can be increased by, for example, removing impurity ions using an ion exchange resin, removing foreign matter using a filter, distillation, or other operations. Specifically, as the water, for example, deionized water (ion-exchanged water), pure water, ultrapure water, distilled water, etc. are preferably used.
[0074] In addition, the solvent may be an organic solvent or a mixed solvent of water and an organic solvent, if the solubility of the raw water-soluble polymer can be improved. The organic solvent is not particularly limited and any known organic solvent can be used. When a mixed solvent of water and an organic solvent is used, organic solvents that are miscible with water, such as acetone, acetonitrile, ethanol, methanol, isopropanol, glycerin, ethylene glycol, and propylene glycol, are preferably used. When an organic solvent is used, water and an organic solvent may be mixed, and each component may be added to the resulting mixed solvent and dissolved, or these organic solvents may be used without mixing with water, and the raw water-soluble polymer may be dissolved, and then mixed with water. These organic solvents may be used alone or in combination of two or more.
[0075] The dissolving method in the dissolving step is not particularly limited as long as it can dissolve the raw water-soluble polymer in the solvent, but a method of adding the raw water-soluble polymer to the solvent and stirring is preferred. The stirring method is not particularly limited, and a known method can be used as appropriate. The stirring temperature is not particularly limited, but is generally preferably 10 to 40°C. The stirring time is also not particularly limited.
[0076] [Collision process] The water-soluble polymer of the present invention is a water-soluble polymer that has been treated by a method including a step of applying pressure to the solutions obtained through the above-mentioned dissolution step by colliding them with each other (collision step). In the collision step, two or more solutions collide with each other, and as a result, pressure is applied to these solutions. There are no particular limitations on the device for applying pressure to the solutions, and known devices can be used. A preferred example is a jet mill.
[0077] A jet mill is a device that atomizes particles by collision of particles of the material to be treated with each other or with the wall of the flow path in a liquid phase flow. More specifically, it is a general term for a device that generates a high-speed flow by any method, causes collisions between the liquids to be treated with each other or with the wall of the flow path, and effectively utilizes the turbulence, shear, and cavitation effects caused by the high-speed flow to atomize the raw materials in the liquid to be treated and promote dispersion. Representative methods include a method in which the liquid to be treated is sprayed from a nozzle by a plunger pump or a rotary pump, etc., and collides with a fixed plate at high speed, and a method in which the sprayed liquids to be treated collide with each other from the front. When the liquid to be treated passes through the nozzle in the flow path at high speed or passes while colliding, it is subjected to turbulence and shear, and when the pressure is released immediately after the collision, a cavitation effect occurs, and the raw materials in the liquid to be treated are subjected to the shock of the sudden release of pressure, and are significantly atomized. In the present invention, a method in which the sprayed liquids to be treated collide with each other from the front is used. This makes it possible to prevent impurities from being mixed in.
[0078] The jet mill is particularly excellent in selectively removing the high molecular weight of the raw water-soluble polymer. Here, the selectively removing effect of the high molecular weight means that (1) the amount of the high molecular weight is reduced, (2) the amount of the low molecular weight is maintained, and (3) the peak top molecular weight (peak top molecular weight: Mp) in the differential molecular weight distribution curve described later is maintained. This further increases the filterability of the solution containing the water-soluble polymer to be treated, the polishing composition and / or the wetting agent for semiconductors, and further reduces the number of defects (LPD-N, LPD, etc.) on the substrate polished and / or rinsed by the polishing composition and / or the wetting agent for semiconductors.
[0079] The jet mill is not particularly limited, and for example, a known technique described in JP 2015-188853 A can be used. In addition, a commercially available device such as Starburst Lab (manufactured by Sugino Machine Co., Ltd.) can be used.
[0080] The treatment conditions for the jet mill vary depending on the apparatus used, and are not particularly limited. They can be appropriately adjusted depending on the object of the collision step, the desired effect of selectively removing high molecular weight materials after the collision step, and the like.
[0081] For example, the treatment pressure is not particularly limited, but is preferably 5 MPa or more, more preferably 10 MPa or more, even more preferably 15 MPa or more, and even more preferably 20 MPa or more, and may be, for example, 30 MPa or more, 40 MPa or more, 50 MPa or more, 100 MPa or more, or 200 MPa or more. In this range, the selective removal effect of high molecular weight substances is higher. In addition, the filterability of the solution containing the water-soluble polymer to be treated, the polishing composition and / or the wetting agent for semiconductors is further improved. In addition, the treatment pressure is not particularly limited, but is preferably 900 MPa or less, more preferably 500 MPa or less, and even more preferably 250 MPa or less. In this range, the amount of low molecular weight substances is maintained, and the change in peak top molecular weight (Mp) is smaller.
[0082] The treatment time is not particularly limited, but is preferably 1 minute or more, more preferably 10 minutes or more, even more preferably 20 minutes or more, and even more preferably 30 minutes or more, and may be, for example, 40 minutes or more, 80 minutes or more, or 100 minutes or more. In this range, the selective removal effect of high molecular weight substances is higher. In addition, the filterability of the solution containing the water-soluble polymer to be treated, the polishing composition and / or the wetting agent for semiconductors is further improved. In addition, the treatment time is not particularly limited, but is preferably 600 minutes or less, more preferably 500 minutes or less, and even more preferably 400 minutes or less, and may be, for example, 300 minutes or less, 200 minutes or less, or 150 minutes or less. In this range, the amount of low molecular weight substances is maintained, and the change in peak top molecular weight (Mp) is smaller.
[0083] Furthermore, the flow rate of the treatment liquid is not particularly limited, but is preferably 10 mL / min or more, more preferably 50 mL / min or more, and even more preferably 80 mL / min or more. In this range, the selective removal effect of high molecular weight substances is higher. In addition, the filterability of the solution containing the water-soluble polymer to be treated, the polishing composition and / or the wetting agent for semiconductors is further improved. In addition, the flow rate of the treatment liquid is preferably 100,000 mL / min or less, more preferably 10,000 mL / min or less, even more preferably 1000 mL / min or less, even more preferably 800 mL / min or less, and particularly preferably 600 mL / min or less. In this range, the amount of low molecular weight substances is maintained, and the change in peak top molecular weight (Mp) is smaller.
[0084] The number of times of treatment is not particularly limited, but may be, for example, one or more times, preferably three or more times, and more preferably five or more times. Within this range, the selective removal effect of high molecular weight substances is higher. Also, the filterability of the solution containing the water-soluble polymer to be treated, the polishing composition and / or the wetting agent for semiconductors is improved. Also, the number of times of treatment is preferably 20 times or less, more preferably 10 times or less, and even more preferably 8 times or less. Within this range, the amount of low molecular weight substances is maintained, and the change in peak top molecular weight (Mp) is smaller.
[0085] (Water-soluble polymer to be treated) As described above, the water-soluble polymer to be treated is preferably one from which high molecular weight components of the raw water-soluble polymer have been selectively removed by the collision step, and it is also preferable that the amount of low molecular weight components is maintained and the change in peak top molecular weight (Mp) is small.
[0086] In this specification, the term "high molecular weight component" refers to a component having a higher molecular weight than the peak top molecular weight (Mp). More specifically, it refers to a component corresponding to a LogM on the higher molecular weight side than the LogM at which dw / d(LogM) peaks in the differential molecular weight distribution curve of the water-soluble polymer.
[0087] In this specification, the term "low molecular weight component" refers to a component having a molecular weight lower than the peak top molecular weight (Mp). More specifically, the term refers to a component corresponding to a LogM on the lower molecular weight side than the LogM at which dw / d(LogM) peaks in the differential molecular weight distribution curve of a water-soluble polymer.
[0088] The water-soluble polymer to be treated in the present invention is not particularly limited, but from the viewpoint of selectively removing high molecular weight components of the starting water-soluble polymer, it is preferable that the water-soluble polymer has at least any one of the following characteristics [1] to [3]. Moreover, the water-soluble polymer preferably has two or more of the following characteristics [1] to [3], and more preferably has all of the characteristics.
[0089] [1] Reduction in the amount of high molecular weight substances The change in the amount of high molecular weight components in the treated water-soluble polymer can be confirmed as follows: (1) Draw differential molecular weight distribution curves for the raw water-soluble polymer and the treated water-soluble polymer, respectively. (2) Extract LogM(R) and LogM(P), which are the larger of the two values of LogM on the horizontal axis when the value of dw / d(LogM) on the vertical axis is 20. (3) Compare LogM(P) of the treated water-soluble polymer with LogM(R) of the raw water-soluble polymer. Here, if LogM(P) is smaller than LogM(R), it can be said that the amount of high molecular weight components has decreased.
[0090] Since the reduction amount of the high molecular weight substance is preferably as large as possible, the LogM(P) / LogM(R) ratio (the ratio of LogM(P) to LogM(R)) (%) is preferably as small as possible. The ratio is, for example, preferably 98% or less, more preferably 85% or less, even more preferably 80% or less, even more preferably 65% or less, particularly preferably 60% or less, and even more particularly preferably 45% or less. When the ratio is within the above range, the polishing composition and / or wetting agent for semiconductors according to the present invention is densely adsorbed to the wafer, so that surface defects can be further reduced. The ratio can be lowered by increasing the pressure applied to the solution in the collision step. In the jet mill treatment, for example, the ratio can be lowered by increasing the treatment pressure.
[0091] [2] Maintaining the amount of low molecular weight substances The change in the amount of low molecular weight substances in the treated water-soluble polymer can be confirmed as follows: (1) Draw the differential molecular weight distribution curves of the raw water-soluble polymer and the treated water-soluble polymer, respectively. (2) Extract the vertical axis dw / d(LogM) of the raw water-soluble polymer and the treated water-soluble polymer, respectively, when the horizontal axis LogM value is 4.5. (3) Compare the dw / d(LogM(p)) of the treated water-soluble polymer with the dw / d(LogM(r)) of the raw water-soluble polymer. Here, if the difference between dw / d(LogM(p)) and dw / d(LogM(r)) is small, it can be said that the amount of low molecular weight substances is maintained.
[0092] Since the change in the amount of low molecular weight substances is preferably as small as possible, the ratio of [dw / d(LogM(p))] / [dw / d(LogM(r))] (the ratio of dw / d(LogM(p)) to dw / d(LogM(r))) (%) is preferably closer to 100%. The range may be, for example, 100±5%, preferably 100±3%, more preferably 100±2%, even more preferably 100±1%, even more preferably 100±0.8%, particularly preferably 100±0.5%, even more particularly preferably 100±0.3%, and extremely preferably 100±0.1%. When the ratio is within the above range, it is considered that the function of closely protecting the wafer, which is exerted by the low molecular weight substances of the raw water-soluble polymer, can be maintained. Therefore, surface defects can be further reduced when polishing is performed using a polishing composition containing the above-mentioned treated water-soluble polymer and / or a semiconductor wetting agent containing the water-soluble polymer according to the present invention.
[0093] [3] Maintaining peak top molecular weight (Mp) The change in the peak top molecular weight (Mp) of the treated water-soluble polymer can be confirmed as follows: (1) Draw the differential molecular weight distribution curves of the raw water-soluble polymer and the treated water-soluble polymer, respectively. (2) Extract the LogM at which dw / d(LogM) peaks. (3) Compare the LogM(p_peak) of the treated water-soluble polymer with the LogM(r_peak) of the raw water-soluble polymer. If the difference between LogM(p_peak) and LogM(r_peak) is small, it can be said that the change in the peak top molecular weight (Mp) is small.
[0094] Since the change in peak top molecular weight (Mp) is preferably as small as possible, the ratio of LogM(p_peak) / LogM(r_peak) (the ratio of LogM(p_peak) to LogM(r_peak)) (%) is preferably closer to 100%. The range is, for example, preferably 100±5%, more preferably 100±4%, even more preferably 100±3%, even more preferably 100±2%, particularly preferably 100±1.5%, even more particularly preferably 100±1%, extremely preferably 100±0.5%, and even extremely preferably 100±0.1. When the ratio is within the above range, it is considered that the function of protecting the wafer more uniformly can be maintained. Therefore, the surface defects during polishing using the polishing composition containing the above-mentioned treated water-soluble polymer and / or the semiconductor wetting agent according to the present invention can be further reduced.
[0095] The differential molecular weight distribution curve of the polymer can be prepared by a general method, and the details of the preparation method are described in the Examples. The GPC dissolution curve obtained by the measurement by the GPC method and the area in the differential molecular weight distribution curve can be calculated by using the analysis software installed in the GPC device (manufactured by Tosoh Corporation, product name "HLC-8420 GPC").
[0096] The water-soluble polymer to be treated has the following properties in addition to the above characteristics [1] to [3].
[0097] The Mw / Mn of the treated water-soluble polymer is not particularly limited, but is preferably 30 or less, more preferably 25 or less, even more preferably 20 or less, even more preferably 15 or less, particularly preferably 10 or less, and even more particularly preferably 8 or less, and may be, for example, 7.5 or less (typically 7 or less). Within this range, the number of defects (e.g., LPD-N and LPD) in the substrate polished by the polishing composition and / or semiconductor wetting agent containing the treated water-soluble polymer can be further reduced. In addition, the solution, polishing composition and / or semiconductor wetting agent containing the treated water-soluble polymer have better filterability. In addition, the Mw / Mn of the treated water-soluble polymer is preferably 1 or more.
[0098] The ratio (%) of the dispersity (Mw / Mn) of the water-soluble polymer to be treated to the dispersity (Mw / Mn) of the raw water-soluble polymer is preferably low. The ratio is not particularly limited, but is preferably 90% or less, more preferably 80% or less, even more preferably 75% or less, even more preferably 70% or less, particularly preferably 30% or less, even more particularly preferably 25% or less, and extremely preferably 20% or less. The smaller the ratio, the narrower the molecular weight distribution is, and the more uniform the weight molecular weight of the water-soluble polymer to be treated is. The ratio is preferably 1% or more, more preferably 5% or more, even more preferably 10% or more, and particularly preferably 15% or more. When the ratio is within the above range, the amount of low molecular weight substances tends to be maintained. When the ratio is within the above range, the particle size of the raw water-soluble polymer becomes more uniform, and the wafer can be protected more closely. Therefore, the surface defects during polishing and / or rinsing using the polishing composition and / or semiconductor wetting agent containing the water-soluble polymer to be treated can be further reduced. This ratio can be reduced by increasing the pressure applied to the solution in the collision step, and in the jet mill process, for example, by increasing the process pressure.
[0099] The treated water-soluble polymer obtained through the collision process has the advantage that the difference between the amount of impurities in the treated water-soluble polymer and the amount of impurities in the raw water-soluble polymer is small. In particular, the difference in the amount of metal impurities is small. In the collision process, the solutions are collided with each other to apply pressure to the solution, and collision with other members is not used, so it is considered that impurities are less likely to be mixed in. The amount of metal impurities can be evaluated by measuring the metal impurity concentration using inductively coupled plasma (ICP) optical emission spectrometry, and the measurement device can be, for example, an inductively coupled plasma spectrometer "ICP-AES" manufactured by Shimadzu Corporation. Depending on the type of metal impurity, it may be performed using an inductively coupled plasma mass spectrometer (ICP-MS) or an atomic absorption spectrometer.
[0100] <Method for producing polishing composition and wetting agent for semiconductor> One aspect of the present invention relates to a method for producing a polishing composition containing abrasive grains and a water-soluble polymer (a water-soluble polymer to be treated), the method including a step of dissolving the raw water-soluble polymer in a solvent to prepare a solution (dissolving step), a step of colliding the solutions with each other and applying pressure to the solution (collision step), and a step of mixing abrasive grains into the pressurized solution.
[0101] Another aspect of the present invention relates to a method for producing a wetting agent for a semiconductor, comprising a water-soluble polymer (a water-soluble polymer to be treated), the method comprising a dissolving step, a collision step, and a step of mixing other components into the solution under pressure.
[0102] In these embodiments, the water-soluble polymer to be treated is as described above in the description of the treatment of the water-soluble polymer and the water-soluble polymer to be treated, and the dissolving step and the collision step are as described above in the description of the treatment of the water-soluble polymer and the water-soluble polymer to be treated.
[0103] In addition, the method for producing the polishing composition and / or the wetting agent for semiconductor according to one embodiment of the present invention may include a plurality of mixing steps, and in this case, other steps may be included between each mixing step. For example, after the mixing step for a certain component, a filtration step as described below may be provided, and then a mixing step for another component as described below may be provided.
[0104] [Mixing process] The polishing composition of the present invention is produced by a method including a step (mixing step) of mixing other components including at least abrasive grains with the solution obtained through the collision step. Here, the other components are components other than the water-soluble polymer to be treated obtained from the raw water-soluble polymer through the dissolution step and collision step, and the solvent used in the dissolution step and collision step. Examples of the other components include various components used in known polishing compositions, such as basic compounds, organic acids or salts thereof, inorganic acids or salts thereof, surfactants, chelating agents, preservatives, fungicides, water-soluble polymers other than the water-soluble polymer to be treated, and dispersants. These other components can be mixed to the extent that the effect of the present invention is not significantly hindered. An example of the other components including at least abrasive grains is, for example, only abrasive grains.
[0105] Furthermore, the wetting agent for semiconductors of the present invention is produced by a method including a step (mixing step) of mixing the above-mentioned other components into the solution obtained through the above-mentioned collision step without mixing abrasive grains.
[0106] The mixing method, mixing conditions, etc. of the various components in the mixing step are not particularly limited. For example, the various components may be added to the solution obtained through the collision step, or the solution obtained through the collision step may be added to the various components. The order of addition of the various components is also not particularly limited, and they may be added simultaneously, sequentially, or only some components may be added simultaneously. The mixing temperature is not particularly limited, but is generally preferably 10 to 40°C, and may be heated to increase the dissolution rate. The mixing time is also not particularly limited. The mixing device is also not particularly limited. For example, well-known mixing devices such as a blade type agitator, an ultrasonic disperser, and a homomixer can be used.
[0107] The various components added in the mixing step will be described below.
[0108] (Abrasive grain) The material and properties of the abrasive grains are not particularly limited, and can be appropriately selected according to the purpose and mode of use of the polishing composition. Examples of the abrasive grains include inorganic particles, organic particles, and organic-inorganic composite particles. Specific examples of inorganic particles include oxide particles such as silica particles, alumina particles, cerium oxide particles, chromium oxide particles, titanium dioxide particles, zirconium oxide particles, magnesium oxide particles, manganese dioxide particles, zinc oxide particles, and red iron oxide particles; nitride particles such as silicon nitride particles and boron nitride particles; carbide particles such as silicon carbide particles and boron carbide particles; diamond particles; carbonates such as calcium carbonate and barium carbonate, and the like. Specific examples of organic particles include polymethylmethacrylate (PMMA) particles, poly(meth)acrylic acid particles, and polyacrylonitrile particles. Here, (meth)acrylic acid refers to acrylic acid and methacrylic acid in a comprehensive sense. Such abrasive grains may be used alone or in combination of two or more types. Note that abrasive grains are not included in the wetting agent for semiconductors.
[0109] The above-mentioned abrasive grains are preferably inorganic particles, and among them, particles made of metal or semimetal oxides are preferred, and silica particles are particularly preferred. In a polishing composition that can be used for polishing a substrate having a surface made of silicon, such as a silicon wafer described later, for example, for finish polishing, it is particularly meaningful to adopt silica particles as the abrasive grains. The technology disclosed herein can be preferably implemented, for example, in an embodiment in which the above-mentioned abrasive grains are substantially made of silica particles. Here, "substantially" means that 95% by mass or more of the particles constituting the abrasive grains are silica particles. 98% by mass or more, preferably 99% by mass or more, for example 100% by mass of the particles constituting the abrasive grains may be silica particles.
[0110] Specific examples of silica particles include colloidal silica, fumed silica, precipitated silica, etc. The silica particles can be used alone or in combination of two or more. Colloidal silica is particularly preferred because it is easy to obtain a polished surface with excellent surface quality after polishing. As colloidal silica, for example, colloidal silica produced by ion exchange using water glass (Na silicate) as a raw material, or alkoxide colloidal silica can be preferably used. Here, alkoxide colloidal silica refers to colloidal silica produced by hydrolysis and condensation reaction of alkoxysilane. Colloidal silica can be used alone or in combination of two or more.
[0111] The true specific gravity of the abrasive grain material is preferably 1.5 or more, more preferably 1.6 or more. The abrasive grain material is, for example, silica constituting silica particles. The physical polishing ability tends to increase with an increase in the true specific gravity of the abrasive grain material. When the physical polishing ability of the abrasive grain increases, the local stress that the abrasive grain exerts on the substrate surface generally tends to increase. From this viewpoint, abrasive grains having a true specific gravity of 1.7 or more are particularly preferred. The upper limit of the true specific gravity of the abrasive grains is not particularly limited, but is typically 2.3 or less, for example 2.2 or less. The true specific gravity of the abrasive grains (for example, silica particles) can be measured by a liquid substitution method using ethanol as a substitution liquid.
[0112] The average primary particle diameter (BET diameter) of the abrasive grains is not particularly limited, but from the viewpoint of polishing efficiency, etc., it is preferably 5 nm or more, more preferably 10 nm or more, and even more preferably 15 nm or more. From the viewpoint of obtaining a higher polishing effect, for example, the effect of reducing haze and removing defects, the BET diameter is preferably 15 nm or more, more preferably 20 nm or more, for example, more than 20 nm. From the viewpoint of suppressing the local stress that the abrasive grains give to the substrate surface, the average primary particle diameter of the abrasive grains is preferably 100 nm or less, more preferably 80 nm or less, and even more preferably 60 nm or less. The technology disclosed herein can also be preferably implemented in an embodiment using abrasive grains with an average primary particle diameter of 50 nm or less, typically less than 40 nm, more preferably 35 nm or less, and even more preferably 32 nm or less, because a higher quality surface is easily obtained.
[0113] The average primary particle diameter of the abrasive grains is calculated, for example, from the specific surface area measured by the BET method. The specific surface area of the abrasive grains can be measured, for example, using a "Flow SorbII 2300" manufactured by Micromeritics. In this specification, the BET diameter is calculated from the specific surface area (BET value) measured by the BET method, as follows: BET diameter (nm) = 6000 / (true density (g / cm 3 ) × BET value (m 2 / g)
[0114] The average secondary particle diameter of the abrasive grains is not particularly limited, but from the viewpoint of polishing efficiency, etc., it is preferably 10 nm or more, more preferably 15 nm or more, even more preferably 20 nm or more, and particularly preferably 25 nm or more. From the viewpoint of obtaining a higher polishing effect, for example, the effect of reducing haze and removing defects, the average secondary particle diameter is preferably 30 nm or more, more preferably 40 nm or more. In addition, from the viewpoint of suppressing the local stress that the abrasive grains give to the substrate surface, the average secondary particle diameter of the abrasive grains is preferably 300 nm or less, more preferably 200 nm or less, even more preferably 150 nm or less, and even more preferably 125 nm or less. The technology disclosed herein is also preferably used in an embodiment using abrasive grains having an average secondary particle diameter of 100 nm or less, for example, less than 80 nm (typically 45 nm or less), because it is easy to obtain a higher quality surface, and the stability of the polishing composition is improved by the reduction in the average secondary particle diameter of the abrasive grains that can be implemented. The average secondary particle size of the abrasive grains can be measured by a dynamic light scattering method using, for example, a model "UPA-UT151" manufactured by Nikkiso Co., Ltd.
[0115] The shape (outer shape) of the abrasive grains may be spherical or non-spherical. Specific examples of non-spherical grains include peanut-shaped, i.e., peanut shell-shaped, cocoon-shaped, confetti-shaped, rugby ball-shaped, etc. For example, abrasive grains in which most of the grains are peanut-shaped may be preferably used.
[0116] Although not particularly limited, the average value of the long axis / short axis ratio of the abrasive grains, i.e., the average aspect ratio, is in principle 1.0 or more, preferably 1.05 or more, and more preferably 1.1 or more. By increasing the average aspect ratio, a higher polishing efficiency can be realized. Moreover, from the viewpoint of reducing scratches, etc., the average aspect ratio of the abrasive grains is preferably 3.0 or less, more preferably 2.0 or less, and even more preferably 1.5 or less.
[0117] The shape (outer shape) and average aspect ratio of the abrasive grains can be grasped, for example, by observation with an electron microscope. As a specific procedure for grasping the average aspect ratio, for example, a scanning electron microscope (SEM) is used to draw the smallest rectangle circumscribing each particle image for a predetermined number of silica particles whose individual particle shapes can be recognized. The predetermined number is, for example, 200. Then, for the rectangle drawn for each particle image, the value obtained by dividing the length of its long side (value of the long axis) by the length of its short side (value of the short axis) is calculated as the long axis / short axis ratio (aspect ratio). The average aspect ratio can be obtained by arithmetically averaging the aspect ratios of the above-mentioned predetermined number of particles.
[0118] (Water-soluble polymer) The polishing composition and / or wetting agent for semiconductors of the present invention contains the above-mentioned water-soluble polymer to be treated. The raw water-soluble polymer of the water-soluble polymer to be treated may contain two or more kinds of water-soluble polymers. Preferably, the raw water-soluble polymer of the water-soluble polymer to be treated is one kind of water-soluble polymer.
[0119] The content of the water-soluble polymer to be treated in the polishing composition and / or wetting agent for semiconductors is not particularly limited, but from the viewpoint of surface quality after the polishing and / or rinsing process, it is preferably 0.0001 parts by mass or more relative to 100 parts by mass of the solvent, more preferably 0.0005 parts by mass or more, more preferably 0.001 parts by mass or more, even more preferably 0.0015 parts by mass or more, and particularly preferably 0.002 parts by mass or more, and may be, for example, 0.05 parts by mass or more (typically, 0.1 parts by mass or more). In addition, the content of the water-soluble polymer to be treated in the polishing composition and / or wetting agent for semiconductors is, from the viewpoint of filterability, preferably 5 parts by mass or less relative to 100 parts by mass of the solvent, more preferably 3 parts by mass or less, more preferably 2 parts by mass or less, even more preferably 1 part by mass or less, and particularly preferably 0.5 parts by mass or less, and may be, for example, 0.3 parts by mass or less (typically, 0.2 parts by mass or less).
[0120] The polishing composition and / or semiconductor wetting agent according to one embodiment of the present invention may contain a water-soluble polymer other than the water-soluble polymer to be treated (hereinafter also referred to as "optional polymer"), as long as the effect of the present invention is not significantly hindered. Examples of the optional polymer include the water-soluble polymers exemplified in the dissolution step. Examples of water-soluble polymers other than the exemplified types include polyisoprene sulfonic acid, polyvinyl sulfonic acid, polyallyl sulfonic acid, polyisoamylene sulfonic acid, polystyrene sulfonate, polyacrylate, polyvinyl acetate, etc. The optional polymer may be used alone or in combination of two or more.
[0121] The content of optional polymer in the polishing composition and / or semiconductor wetting agent is not particularly limited, but may be the content of the water-soluble polymer to be treated described in the above mixing step.The ratio of the content of the water-soluble polymer to be treated and the content of optional polymer is not particularly limited, but from the viewpoint of surface quality after polishing step, the ratio of optional polymer to the total water-soluble polymer contained is preferably 70% or less, more preferably 60% or less, more preferably 50% or less, even more preferably 40% or less, even more preferably 30% or less, particularly preferably 20% or less, for example, may be 10% or less, may be 5% or less.
[0122] In one embodiment of the present invention, when the polishing composition and / or the wetting agent for semiconductors is in a concentrated state, the content of the water-soluble polymer in the polishing composition and / or the wetting agent for semiconductors is preferably 0.0001% by mass or more, more preferably 0.0005% by mass or more, even more preferably 0.001% by mass or more, and particularly preferably 0.01% by mass or more, from the viewpoint of improving stability. In one embodiment of the present invention, when the polishing composition and / or the wetting agent for semiconductors is in a concentrated state, the content of the water-soluble polymer in the polishing composition and / or the wetting agent for semiconductors is preferably 5% by mass or less, more preferably 3% by mass or less, and even more preferably 1% by mass or less, from the viewpoint of storage stability, filterability, etc.
[0123] In one embodiment of the present invention, when the polishing composition and / or the wetting agent for semiconductors is in a diluted state, the content of the water-soluble polymer is preferably 0.00005% by mass or more, more preferably 0.0001% by mass or more, even more preferably 0.0005% by mass or more, and particularly preferably 0.001% by mass or more, from the viewpoint of improving the surface quality after the polishing and / or rinsing process. In addition, in one embodiment of the present invention, when the polishing composition and / or the wetting agent for semiconductors is in a diluted state, the content of the water-soluble polymer is preferably 0.1% by mass or less, more preferably 0.05% by mass or less, and even more preferably 0.01% by mass or less, from the viewpoint of maintaining the polishing rate. In addition, in the above, the content of the water-soluble polymer refers to the total amount when the polishing composition and / or the wetting agent for semiconductors contains two or more water-soluble polymers.
[0124] (Dispersant) The dispersion medium contained in the polishing composition and / or the wetting agent for semiconductor is not particularly limited, but for example, it is preferable to use the type exemplified in the above dissolving step.In particular, it is preferable to use the solvent used in the above dissolving step and / or the above collision step as it is.Note that the solvent used in the above dissolving step and / or the above collision step usually functions as a dispersion medium in the polishing composition and / or the wetting agent for semiconductor, especially for abrasive grains.
[0125] (Basic compounds) In this specification, the basic compound refers to a compound that dissolves in water and has the function of increasing the pH of the aqueous solution. As the basic compound, an organic or inorganic basic compound containing nitrogen, an alkali metal hydroxide, an alkaline earth metal hydroxide, various carbonates and hydrogen carbonates, etc. can be used. Examples of the basic compound containing nitrogen include a quaternary ammonium compound, a quaternary phosphonium compound, ammonia, and an amine. The amine is preferably a water-soluble amine. Such a basic compound can be used alone or in combination of two or more.
[0126] Specific examples of hydroxides of alkali metals include potassium hydroxide and sodium hydroxide. Specific examples of carbonates or hydrogen carbonates include ammonium hydrogen carbonate, ammonium carbonate, potassium hydrogen carbonate, potassium carbonate, sodium hydrogen carbonate, and sodium carbonate. Specific examples of amines include methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, monoethanolamine, N-(β-aminoethyl)ethanolamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, anhydrous piperazine, piperazine hexahydrate, 1-(2-aminoethyl)piperazine, N-methylpiperazine, guanidine, azoles such as imidazole and triazole, and the like. Specific examples of quaternary phosphonium compounds include quaternary phosphonium hydroxides such as tetramethylphosphonium hydroxide and tetraethylphosphonium hydroxide.
[0127] As the quaternary ammonium compound, a quaternary ammonium salt such as a tetraalkylammonium salt or a hydroxyalkyltrialkylammonium salt can be preferably used. A quaternary ammonium salt is typically a strong base. The anion component in such a quaternary ammonium salt is, for example, OH - , F - , Cl - , Br - , I - , ClO4 - , BH4 - etc. In particular, a preferred example is one in which the anion is OH - Specific examples of quaternary ammonium hydroxides include tetraalkylammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetrapentylammonium hydroxide, and tetrahexylammonium hydroxide; hydroxyalkyltrialkylammonium hydroxides such as 2-hydroxyethyltrimethylammonium hydroxide (also called choline); and the like.
[0128] Among these basic compounds, at least one basic compound selected from, for example, alkali metal hydroxide, quaternary ammonium hydroxide, and ammonia can be preferably used. Among them, tetraalkylammonium hydroxide and ammonia are more preferable, and ammonia is particularly preferable. As the tetraalkylammonium hydroxide, for example, tetramethylammonium hydroxide can be mentioned.
[0129] When the polishing composition and / or wetting agent for semiconductor disclosed herein contains a basic compound, the content of the basic compound in the polishing composition and / or wetting agent for semiconductor is not particularly limited.From the viewpoint of suitable processing of the substrate surface, the content is usually preferably 0.0001 mass% or more of the polishing liquid in the concentrated liquid or diluted liquid, and more preferably 0.0005 mass% or more, for example, 0.001 mass% or more, typically 0.002 mass% or more.In addition, from the viewpoint of improving surface quality, the content is suitably less than 15 mass%, preferably less than 10 mass%, more preferably less than 5 mass%, more preferably less than 1.0 mass%, and even more preferably less than 0.5 mass%.
[0130] (Organic acid or its salt, inorganic acid or its salt) Examples of organic acids include fatty acids such as formic acid, acetic acid, and propionic acid, aromatic carboxylic acids such as benzoic acid and phthalic acid, citric acid, oxalic acid, tartaric acid, malic acid, maleic acid, fumaric acid, succinic acid, organic sulfonic acids, and organic phosphonic acids. Examples of organic acid salts include alkali metal salts of organic acids, such as sodium salts, potassium salts, and ammonium salts. Examples of inorganic acids include sulfuric acid, nitric acid, hydrochloric acid, and carbonic acid. Examples of inorganic acid salts include alkali metal salts of inorganic acids, such as sodium salts, potassium salts, and ammonium salts. Organic acids and their salts, and inorganic acids and their salts can be used alone or in combination of two or more.
[0131] (Oxidizing agent) Examples of oxidizing agents include hydrogen peroxide (H2O2), sodium persulfate, ammonium persulfate, sodium dichloroisocyanurate, etc. The polishing composition and semiconductor wetting agent disclosed herein are preferably substantially free of oxidizing agents. If the polishing composition and / or semiconductor wetting agent contain an oxidizing agent, the surface of the polishing object is oxidized to generate an oxide film by supplying the polishing composition and / or semiconductor wetting agent to the object to be polished. This may result in a decrease in the surface quality of the substrate, or a decrease in the action of the polishing composition and / or semiconductor wetting agent on the substrate surface. The substrate is, for example, a silicon wafer. Note that the polishing composition and / or semiconductor wetting agent being substantially free of oxidizing agents means that the oxidizing agent is not intentionally contained at least.
[0132] (Surfactant) As the surfactant, any of anionic, cationic, nonionic, and amphoteric surfactants can be used. Usually, anionic or nonionic surfactants can be preferably used. From the viewpoint of low foaming and ease of pH adjustment, nonionic surfactants are more preferable. Examples of nonionic surfactants include oxyalkylene polymers such as polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; polyoxyalkylene derivatives such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene alkylamines, polyoxyethylene fatty acid esters, polyoxyethylene glyceryl ether fatty acid esters, and polyoxyethylene sorbitan fatty acid esters (e.g., polyoxyalkylene adducts); copolymers of multiple types of oxyalkylenes (e.g., diblock copolymers, triblock copolymers, random copolymers, and alternating copolymers); and the like. In one embodiment, surfactants containing a polyoxyalkylene structure (e.g., polyoxyethylene structure, polyoxypropylene structure, etc.) in one molecule can be preferably used. The surfactants can be used alone or in combination of two or more types.
[0133] (chelating agent) Examples of the chelating agent include aminocarboxylic acid chelating agents and organic phosphonic acid chelating agents. Examples of the aminocarboxylic acid chelating agent include ethylenediaminetetraacetic acid, sodium ethylenediaminetetraacetate, nitrilotriacetic acid, sodium nitrilotriacetate, ammonium nitrilotriacetate, hydroxyethylethylenediaminetriacetic acid, sodium hydroxyethylethylenediaminetriacetate, diethylenetriaminepentaacetic acid, sodium diethylenetriaminepentaacetate, triethylenetetraminehexaacetic acid, and sodium triethylenetetraminehexaacetate. Examples of organic phosphonic acid chelating agents include 2-aminoethylphosphonic acid, 1-hydroxyethylidene-1,1-diphosphonic acid, aminotri(methylenephosphonic acid), ethylenediaminetetrakis(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid), ethane-1,1-diphosphonic acid, ethane-1,1,2-triphosphonic acid, ethane-1-hydroxy-1,1-diphosphonic acid, ethane-1-hydroxy-1,1,2-triphosphonic acid, ethane-1,2-dicarboxy-1,2-diphosphonic acid, methanehydroxyphosphonic acid, 2-phosphonobutane-1,2-dicarboxylic acid, 1-phosphonobutane-2,3,4-tricarboxylic acid and α-methylphosphonosuccinic acid.Of these, organic phosphonic acid chelating agents are more preferred. Among them, preferred are ethylenediaminetetrakis(methylenephosphonic acid), diethylenetriaminepenta(methylenephosphonic acid) and diethylenetriaminepentaacetic acid. Particularly preferred are ethylenediaminetetrakis(methylenephosphonic acid) and diethylenetriaminepenta(methylenephosphonic acid). The chelating agent can be used alone or in combination of two or more.
[0134] [Filtration process] The polishing composition and / or semiconductor wetting agent according to one embodiment of the present invention may be produced by a method including a step of filtering a solution used to produce the polishing composition and / or the semiconductor wetting agent (also referred to simply as a "filtration step" in this specification).
[0135] A method for producing a polishing composition and / or a semiconductor wetting agent according to a preferred embodiment of the present invention further comprises, after the collision step and before the mixing step, a step of filtering the solution obtained through the collision step. A method for producing a polishing composition and / or a semiconductor wetting agent according to a preferred embodiment of the present invention further comprises, after the mixing step, a step of filtering the solution obtained through the mixing step. Note that the production method according to one embodiment of the present invention may further comprise a step of filtering the solution at both of the above timings.
[0136] The material of the filter used in the filtration step is not particularly limited, and examples thereof include resins such as cellulose mixed esters, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), ethylene-tetrafluoroethylene copolymer, polycarbonate, polyethersulfone, cellulose acetate, nitrocellulose, regenerated cellulose, polyamide, triacetyl cellulose, polypropylene, polyvinyl chloride (PVC), nylon, nylon 66, polysulfone, polyester, polypropylene / polyethylene, acrylic copolymer, polycarbonate, polylactic acid, polycaprolactone, polyglycolic acid, polydioxanone, polyhydroxybutyrate, polybutadiene, polyurethane, polystyrene (PS), polymethyl methacrylate, and polycarbonate, glass, metal, and the like.
[0137] The structure of the filter is not particularly limited, and examples thereof include a depth structure, a pleated structure, and a membrane structure.
[0138] The pore size of the filter is not particularly limited, but is preferably 0.03 μm or more, more preferably 0.04 μm or more, even more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and particularly preferably 0.2 μm or more. When the pore size of the filter is 0.03 μm or more, for example, 0.04 μm or more, it is preferable because a high filtration speed can be obtained. In addition, the pore size of the filter is preferably 100 μm or less, more preferably 70 μm or less, even more preferably 50 μm or less, even more preferably 15 μm or less, and particularly preferably 1 μm or less (specifically, for example, 0.5 μm or less is preferable). When the pore size of the filter is 100 μm or less, the accuracy of filtration is further improved.
[0139] The filtration method may be any of natural filtration under normal pressure, suction filtration, pressure filtration, and centrifugal filtration.
[0140] [Other processes] The polishing composition and / or semiconductor wetting agent according to one embodiment of the present invention may be produced through further processes other than the dissolution process, the collision process, the mixing process, and the filtration process.
[0141] <Polishing composition, wetting agent for semiconductors> The polishing composition and / or wetting agent for semiconductors of the present invention have the characteristics described below.
[0142] (D90) The D90(P) of the particles in the polishing composition of the present invention is smaller than the D90(R) of the particles in the polishing composition containing the raw water-soluble polymer not treated according to the present invention. Here, D90 refers to the particle size where the cumulative mass from the small particle size side of the cumulative particle size distribution on a volume basis is 90%. The ratio (%) of D90(P) to D90(R) is not particularly limited, but is preferably 99.5% or less, more preferably 95% or less, and even more preferably 90% or less. When the ratio is within this range, the number of defects (e.g., LPD-N and LPD) in the substrate polished and / or rinsed by the polishing composition and / or semiconductor wetting agent can be further reduced. In addition, the dispersibility of the abrasive grains in the polishing composition is improved, and the composition has better filterability. The ratio is preferably 50% or more, more preferably 60% or more, and even more preferably 70% or more. When the ratio is within this range, the particle size becomes too small, and the physical processing force (e.g., polishing rate) can be suppressed from decreasing. The D90 of the polishing composition can be determined by a dynamic light scattering method using UPA-UT151 manufactured by Nikkiso Co., Ltd., and the details of the measurement method will be described in the Examples.
[0143] (pH) The pH of the polishing composition according to one embodiment of the present invention is preferably 8.0 or more, more preferably 8.5 or more, even more preferably 9.0 or more, even more preferably 9.5 or more, and particularly preferably 10.0 or more. When the pH of the polishing composition is high, the polishing efficiency tends to improve. On the other hand, from the viewpoint of preventing dissolution of abrasive grains and suppressing the decrease in mechanical polishing action, the pH of the polishing composition is preferably 13.0 or less, more preferably 12.5 or less, even more preferably 12.0 or less, even more preferably 11.5 or less, particularly preferably 11.0 or less, and even more particularly preferably 10.8 or less, and may be, for example, 10.5 or less, or may be 10.0 or less.
[0144] The pH of the wetting agent for semiconductor according to one embodiment of the present invention is preferably 8.0 or more, more preferably 8.5 or more, even more preferably 9.0 or more, even more preferably 9.5 or more, and particularly preferably 10.0 or more. The pH of the wetting agent for semiconductor is preferably 13.0 or less, more preferably 12.5 or less, even more preferably 12.0 or less, even more preferably 11.5 or less, particularly preferably 11.0 or less, and particularly preferably 10.8 or less, and may be, for example, 10.5 or less, or may be 10.0 or less. When the pH of the wetting agent for semiconductor is within the above range, the surface of the substrate can be suitably treated.
[0145] The pH can be determined by using a pH meter, performing three-point calibration using a standard buffer solution, placing a glass electrode in the composition to be measured, and measuring the value after 2 minutes or more have elapsed and the value has stabilized. For example, LAQUA (registered trademark) manufactured by Horiba, Ltd. or an equivalent product can be used as the pH meter. For the standard buffer solution, a phthalate pH buffer solution, pH: 4.01 (25°C), a neutral phosphate pH buffer solution, pH: 6.86 (25°C), or a carbonate pH buffer solution, pH: 10.01 (25°C) can be used.
[0146] <Polishing and rinsing method> One aspect of the present invention is a method for polishing a substrate using a polishing composition containing abrasive grains and a water-soluble polymer to be treated. Another aspect of the present invention is a method for rinsing a substrate using a wetting agent for semiconductors containing the water-soluble polymer to be treated.
[0147] In these embodiments, the abrasive grains are the same as those described above in the description of the polishing composition and the method for producing a wetting agent for semiconductors, and the treated water-soluble polymer is the same as those described above in the description of the treatment of the water-soluble polymer and the treated water-soluble polymer.
[0148] Hereinafter, a preferred embodiment of the method for polishing and / or rinsing a substrate using the polishing composition and / or wetting agent for semiconductors according to the present invention will be described.
[0149] First, prepare a polishing liquid and / or a rinsing liquid containing the polishing composition and / or the wetting agent for semiconductors according to the present invention. The preparation of the polishing liquid and / or the rinsing liquid includes adjusting the concentration, pH, etc. of the polishing composition and / or the wetting agent for semiconductors to prepare the polishing liquid and the rinsing liquid. The concentration adjustment can be, for example, dilution. Alternatively, the polishing composition and / or the wetting agent for semiconductors can be used as the polishing liquid and / or the rinsing liquid as it is.
[0150] Next, the polishing liquid and / or rinsing liquid are supplied to the substrate, and polished and / or rinsed in a conventional manner. For example, when performing finish polishing and / or rinsing of a silicon wafer, typically, the silicon wafer that has been subjected to the lapping process is set in a general polishing device, and the polishing liquid and / or rinsing liquid are supplied to the surface to be polished of the silicon wafer through the polishing pad of the polishing device. Typically, while continuously supplying the polishing liquid and / or rinsing liquid, the polishing pad is pressed against the surface to be polished of the silicon wafer, and the two are moved relatively, for example, rotated. Through such a polishing process, polishing and / or rinsing of the substrate is completed.
[0151] The polishing composition and / or wetting agent for semiconductors according to one embodiment of the present invention can be preferably applied to a polishing step or a rinsing step of a substrate such as a silicon wafer, etc. Before the polishing step and / or the rinsing step using the polishing composition and / or the wetting agent for semiconductors according to the present invention, the substrate may be subjected to a general treatment that can be applied to a substrate in a step upstream of the polishing step or the rinsing step, such as lapping or etching.
[0152] The polishing composition and / or wetting agent for semiconductors disclosed herein can be preferably used, for example, in polishing or rinsing a substrate (e.g., silicon wafer) that has been prepared to have a surface roughness of 0.01 nm to 100 nm by an upstream process. The surface roughness Ra of the substrate can be measured, for example, using a laser scanning surface roughness meter "TMS-3000WRC" manufactured by Schmitt Measurement System Inc. The polishing composition and / or wetting agent for semiconductors disclosed herein is effective when used in final polishing (finish polishing) or the polishing immediately before it, or in rinsing, and is particularly preferably used in final polishing. Here, final polishing refers to the last polishing step in the manufacturing process of the target object, that is, a step after which no further polishing is performed. The polishing composition disclosed herein may be used in a polishing step upstream of the final polishing. Here, the polishing step upstream of the final polishing refers to a preliminary polishing step between the rough polishing step and the final polishing step. Typically, this includes at least a primary polishing step, and may further include secondary, tertiary, etc. polishing steps. The semiconductor wetting agent disclosed herein may be used in a rinsing step that is performed after a polishing step upstream of the final polishing.
[0153] (Concentrate) The polishing composition and / or wetting agent for semiconductors disclosed herein may be in a concentrated form before being supplied to a substrate. That is, the polishing composition and / or wetting agent for semiconductors is in the form of a concentrated liquid of a polishing liquid and / or a rinsing liquid, and can also be understood as a stock liquid of a polishing liquid and / or a rinsing liquid. The polishing composition and / or wetting agent for semiconductors in such a concentrated form is advantageous from the viewpoint of convenience and cost reduction during production, distribution, storage, etc. The concentration ratio is not particularly limited, and can be, for example, about 2 to 100 times in volume conversion, and is usually about 5 to 50 times (for example, about 10 to 40 times).
[0154] (Dilution solution) The polishing composition and / or wetting agent for semiconductors disclosed herein is typically supplied to a substrate in the form of a polishing liquid and a rinsing liquid containing the polishing composition and / or wetting agent for semiconductors, and used for polishing and / or rinsing the substrate. The polishing liquid and / or rinsing liquid may be prepared, for example, by diluting any of the polishing compositions and / or wetting agents for semiconductors disclosed herein. The dilution is typically with water. Alternatively, the polishing composition and / or wetting agent for semiconductors may be used as a polishing liquid and / or a rinsing liquid as it is. That is, the concept of the polishing composition and / or wetting agent for semiconductors in the technology disclosed herein includes both a polishing liquid (working slurry) and / or a rinsing liquid that is supplied to a substrate and used for polishing and / or rinsing the substrate, and a concentrated liquid that is diluted and used as a polishing liquid and / or a rinsing liquid, i.e., a stock solution of the polishing liquid and / or a rinsing liquid. Other examples of polishing liquids and / or rinsing liquids containing the polishing composition and / or semiconductor wetting agent disclosed herein include polishing liquids and / or rinsing liquids obtained by adjusting the pH of the composition.
[0155] The content of the abrasive grains in the concentrated liquid is not particularly limited, but may be, for example, 50% by mass or less. From the viewpoint of the handling property of the concentrated liquid, such as the dispersion stability and filterability of the abrasive grains, the content of the abrasive grains in the concentrated liquid is usually preferably 30% by mass or less, more preferably 20% by mass or less, and even more preferably 10% by mass or less. From the viewpoint of convenience and cost reduction during production, distribution, storage, etc., the content of the abrasive grains may be, for example, 0.5% by mass or more, preferably 1% by mass or more, more preferably 2% by mass or more, for example, 3% by mass or more. In a preferred embodiment, the content of the abrasive grains may be 4% by mass or more, or 5% by mass or more.
[0156] The content of the abrasive grains in the dilution is not particularly limited, but may be, for example, 25% by mass or less. From the viewpoint of the handling property of the dilution (for example, dispersion stability of the abrasive grains) and the surface quality after polishing, the content of the abrasive grains in the dilution is usually preferably 10% by mass or less, more preferably 5% by mass or less, even more preferably 1% by mass or less, and particularly preferably 0.5% by mass or less. In addition, from the viewpoint of convenience and cost reduction during production, distribution, storage, etc., the content of the abrasive grains may be, for example, 0.01% by mass or more, preferably 0.1% by mass or more, more preferably 0.2% by mass or more, for example, 0.5% by mass or more. In a preferred embodiment, the content of the abrasive grains may be 1% by mass or more, or 3% by mass or more.
[0157] Such a concentrated solution can be used in a manner in which it is diluted at a desired timing to prepare a polishing solution (working slurry) and / or a rinsing solution, and the polishing solution and / or the rinsing solution are supplied to a substrate. The dilution can be performed, for example, by adding water to the concentrated solution and mixing it.
[0158] The polishing composition and / or semiconductor wetting agent used in the technology disclosed herein may be a one-component type or a multi-component type, including a two-component type. For example, the polishing composition may be configured to prepare a polishing liquid by mixing a part A containing at least abrasive grains among the components of the polishing composition and a part B containing at least a part of the remaining components, and mixing and diluting them at an appropriate time as necessary. Also, the polishing composition may be configured to prepare a rinse liquid by mixing a part A containing a part of the components of the semiconductor wetting agent and a part B containing at least a part of the remaining components, and mixing and diluting them at an appropriate time as necessary.
[0159] (Polishing pad) The polishing pad used in the polishing and / or rinsing step is not particularly limited. For example, a polishing pad of a polyurethane foam type, a nonwoven fabric type, a suede type, etc. can be used. Each polishing pad may contain abrasive grains or may not contain abrasive grains. Usually, a polishing pad that does not contain abrasive grains is preferably used.
[0160] (Washing) The substrate polished and / or rinsed using the polishing composition and / or semiconductor wetting agent according to one embodiment of the present invention is typically cleaned. Cleaning can be performed using an appropriate cleaning liquid. The cleaning liquid used is not particularly limited, and for example, SC-1 cleaning liquid, SC-2 cleaning liquid, etc., which are common in the field of semiconductors, etc., can be used. The SC-1 cleaning liquid can be a mixture of ammonium hydroxide (NH4OH), hydrogen peroxide (H2O2), and water (H2O). The SC-2 cleaning liquid can be a mixture of HCl, H2O2, and H2O. The temperature of the cleaning liquid can be, for example, in the range of room temperature or higher, up to about 90°C. The room temperature is typically about 15°C to 25°C. From the viewpoint of improving the cleaning effect, a cleaning liquid of about 40°C to 85°C can be preferably used.
[0161] (Application) The polishing composition and / or wetting agent for semiconductors according to one embodiment of the present invention can be preferably used for polishing and / or rinsing a surface made of silicon, typically for polishing and / or rinsing a silicon wafer. A typical example of the silicon wafer referred to here is a silicon single crystal wafer (single crystal silicon wafer), for example, a silicon single crystal wafer obtained by slicing a silicon single crystal ingot. The polishing composition and / or wetting agent for semiconductors according to one embodiment of the present invention can be preferably used for polishing and / or rinsing a substrate having a surface made of silicon.
[0162] (substrate) The polishing composition and / or wetting agent for semiconductors according to one embodiment of the present invention can be applied to polishing and / or rinsing substrates having various materials and shapes. The substrate material can be, for example, metals or semimetals such as silicon, aluminum, nickel, tungsten, copper, tantalum, titanium, stainless steel, or alloys thereof; glassy materials such as quartz glass, aluminosilicate glass, and glassy carbon; ceramic materials such as alumina, silica, sapphire, silicon nitride, tantalum nitride, and titanium carbide; compound semiconductor substrate materials such as silicon carbide, gallium nitride, and gallium arsenide; and resin materials such as polyimide resin. The substrate can be made of a plurality of these materials. EXAMPLES
[0163] The present invention will be described in more detail with reference to the following examples and comparative examples. However, the technical scope of the present invention is not limited to the following examples. In addition, unless otherwise specified, "%" and "parts" mean "% by mass" and "parts by mass", respectively.
[0164] <Production of Hydroxyethyl Cellulose> [Dissolution process] Each aqueous solution of raw hydroxyethyl cellulose (aqueous raw HEC solution of HEC) was prepared by adding 2 parts by mass of each of the raw hydroxyethyl celluloses (raw HEC) listed below to 98 parts by mass of deionized water (DIW) as a solvent, mixing and dissolving the mixture so as to obtain the composition shown in Table 1 below.
[0165] (Raw material hydroxyethyl cellulose) HEC1: Weight average molecular weight (Mw): 3.65×10^5, powder, HEC2: Weight average molecular weight (Mw): 1.18×10^6, powder, Here, "10^X" (where X is any integer) is 10 X The same applies below.
[0166] The weight average molecular weight (Mw) of HEC1 and HEC2 indicates a value obtained according to the evaluation method for the weight average molecular weight (Mw) of hydroxyethyl cellulose described below.
[0167] [Collision process] The raw HEC aqueous solution obtained in the dissolution step was placed in a jet mill (manufactured by Sugino Machine Corp., product name: Starburst Lab). The jet mill was then operated at the output (pressure) shown in Table 1 below, and the raw HEC aqueous solution was collided with itself to apply pressure to the raw HEC aqueous solution. The number of treatments was one. The amount of raw HEC aqueous solution treated was approximately 5000 mL, and the treatment liquid flow rate and treatment time were as shown in Table 1 below. The treatment time was calculated by dividing the amount of raw HEC aqueous solution treated by the treatment liquid flow rate.
[0168] [Table 1]
[0169] The raw HEC aqueous solution (treated HEC aqueous solution) that had been subjected to the collision step was collected and then subjected to the following evaluations.
[0170] <Evaluation of Hydroxyethyl Cellulose> Weight average molecular weight, number average molecular weight and molecular weight distribution The weight average molecular weight (Mw), number average molecular weight (Mn), and molecular weight distribution of the hydroxyethyl cellulose in each of the above raw HEC aqueous solutions and each treated HEC aqueous solution were measured by GPC using the following apparatus and conditions. The results using HEC1 as the raw water-soluble polymer are shown in Table 2 below, and the results using HEC2 as the raw water-soluble polymer are shown in Table 3 below.
[0171] [GPC measurement conditions] Measurement equipment: Tosoh Corporation HLC-8420 GPC Column: TSKgel GMPWXL manufactured by Tosoh Corporation Molecular weight marker: Agilent Technologies Polyethylene oxide-polyethylene glycol Eluent: 0.1M NaNO3 Flow rate: 1.0ml / min.
[0172] The GPC elution curves (RI (mV)-elution time (min) curves) obtained by the above-mentioned GPC method were confirmed for the hydroxyethyl cellulose in each of the above-mentioned raw HEC aqueous solutions and each treated HEC aqueous solution. The GPC elution curves when HEC1 was used as the raw water-soluble polymer are shown in Figure 1, and the GPC elution curves when HEC2 was used as the raw water-soluble polymer are shown in Figure 2.
[0173] From these GPC elution curves, the differential molecular weight distribution curves were confirmed. The differential molecular weight distribution curves when HEC1 was used as the raw water-soluble polymer are shown in Figure 3, and the differential molecular weight distribution curves when HEC2 was used as the raw water-soluble polymer are shown in Figure 4. The differential molecular weight distribution curves were created by a general method using the control and analysis software "Eco SEC-WS" used in the above GPC measurement device.
[0174] <Selective removal of high molecular weight substances from treated HEC> It was confirmed that high molecular weight substances were selectively removed from the aqueous solutions containing the above-mentioned treated HEC by measuring (1) the amount of high molecular weight substances before and after the collision step, (2) the amount of low molecular weight substances before and after the collision step, and (3) the change in peak top molecular weight (Mp). The results are shown in Tables 2 and 3 below.
[0175] <Changes in molecular weight distribution before and after the collision process> The molecular weight distribution (Mw / Mn) values obtained by the GPC method for the hydroxyethyl cellulose in each of the raw HEC aqueous solutions and each treated HEC aqueous solution are shown in Tables 2 and 3. The ratio (%) of Mw / Mn of hydroxyethyl cellulose in each treated HEC aqueous solution to Mw / Mn of hydroxyethyl cellulose in each raw HEC aqueous solution is also shown in Tables 2 and 3.
[0176] ≪Amount of metal impurities≫ The amount of metal element impurities was confirmed by measuring the metal impurity concentration of the raw HEC aqueous solution using HEC1 as the raw water-soluble polymer and the treated HEC aqueous solution using inductively coupled plasma (ICP) optical emission spectrometry. The equipment used was Shimadzu Corporation's ICP-AES (model number: ICPS-8100).
[0177] <Filterability> 100 g of each raw HEC aqueous solution and each treated HEC aqueous solution was weighed out and diluted with deionized water (DIW) to prepare a 1% by mass aqueous solution. The prepared aqueous solution was suction filtered using a filter (filter material: polyethersulfone membrane, pore size: 0.2 μm). The liquid passing time (min) was measured. In addition, suction filtration was also performed on 100 g of deionized water (DIW) in the same manner, and the liquid passing time (sec) was measured. The liquid passing time here is the time from the start of filtration until all the liquid passes through the filter. The suction filtration was performed using an aspirator (product name), MDA-015 (model) manufactured by ULVAC, Inc., and the maximum vacuum pressure during the filtration test was about 0.5 kPa. The ratio of the time that the raw HEC aqueous solution or the HEC aqueous solution to be treated passed through to the time that the DIW passed through (time that the raw HEC aqueous solution or the HEC aqueous solution to be treated passed through (min) / time that the DIW passed through (sec)) was evaluated as the filtration index. The smaller the filtration index value, the better the filterability. The results when HEC1 was used as the raw material are shown in Table 2 below, and the results when HEC2 was used as the raw material are shown in Table 3 below.
[0178] [Table 2]
[0179] [Table 3]
[0180] From the results in Table 2 above, it was confirmed that the hydroxyethyl celluloses of Examples 1 to 3 obtained through the above-mentioned dissolution step and collision step have a significantly superior solution filterability, in which the amount of low molecular weight components is well maintained while high molecular weight components are selectively removed, compared with the hydroxyethyl cellulose of Comparative Example 1 which did not undergo the above-mentioned collision step.
[0181] From the results in Table 3 above, it was confirmed that the hydroxyethyl celluloses of Examples 4 to 6 obtained through the above-mentioned dissolution step and collision step have a significantly superior solution filterability, in which the amount of low molecular weight components is well maintained while high molecular weight components are selectively removed, compared with the hydroxyethyl cellulose of Comparative Example 2 which did not undergo the above-mentioned collision step.
[0182] More specifically, it was confirmed that the Mw / Mn ratio of the hydroxyethyl cellulose according to these Examples was reduced to 17% to 87%. It was found that the molecular weight distribution of the hydroxyethyl cellulose was narrowed, and hydroxyethyl cellulose having a uniform weight molecular weight was obtained. It was also confirmed that the amount of high molecular weight components was reduced to 36% to 93%. It was also confirmed that the change in the amount of low molecular weight components was within the range of ±1%. Furthermore, it was confirmed that the change in peak top molecular weight (Mp) was within the range of ±5%.
[0183] In addition, the measurement results of the amount of metal impurities confirmed that the amount of metal impurities in the treated water-soluble polymer did not increase. This result is believed to be due to the fact that the process of colliding the solutions and applying pressure to the solutions, as was carried out in the examples, made it possible to prevent the inclusion of metal impurities.
[0184] <Preparation of Polishing Composition> (Examples 1 to 4, Comparative Examples 1 and 2) The above-mentioned HEC aqueous solution to be treated, abrasive grains, a basic compound, an arbitrary polymer, a surfactant, and deionized water (DIW) were mixed to prepare a concentrated solution of a polishing composition. Colloidal silica with an average primary particle size of 27 nm was used as the abrasive grains, 29% ammonia water was used as the basic compound, polyvinyl alcohol with a weight average molecular weight of 70,000 that was not treated according to the present invention was used as the arbitrary polymer, and a block copolymer of EO and PO (a triblock copolymer of PEO-PPO-PEO type) was used as the surfactant. The obtained concentrated solution of the polishing composition was diluted with deionized water (DIW) to a volume ratio of 20 times to obtain each polishing composition. The concentrations of each component in the concentrated solution of the polishing composition were 0.17 parts by mass of HEC, 3.5 parts by mass of abrasive grains, 0.1 parts by mass of basic compound, 0.001 parts by mass of the arbitrary polymer, and 0.025 parts by mass of surfactant. The concentration of the abrasive grains in the diluted polishing composition was 0.175 mass %, and the concentration of HEC was 0.0085 mass %.
[0185] <Evaluation of Polishing Composition> <D90 measurement> The D90 of the particles present in the polishing composition of this example was measured. For the measurement, UPA-UT151 manufactured by Nikkiso Co., Ltd. was used. The results of using HEC1 as the raw water-soluble polymer are shown in Table 4 below, and the results of using HEC2 as the raw water-soluble polymer are shown in Table 5 below.
[0186] <Polishing test> 12-inch diameter single crystal silicon wafer (conductivity type: P type, crystal orientation: <100> Preliminary polishing was performed under the following conditions, and then main polishing was performed.
[0187] [Preliminary polishing] The polishing solution used in the preliminary polishing was obtained by diluting a concentrated solution of a composition prepared by mixing abrasive grains, a basic compound, and deionized water (DIW) to a volume ratio of 20 times with deionized water (DIW). Colloidal silica with an average primary particle size of 42 nm was used as the abrasive grains, and potassium hydroxide was used as the basic compound. The concentration of the abrasive grains in the diluted polishing solution was 1.0 mass%, and the concentration of the basic compound was 0.068 mass%.
[0188] [Preliminary polishing conditions] Polishing equipment: Okamoto Machine Tool Works' sheet-fed polishing machine, model "PNX-332B" Polishing load: 20kPa Plate rotation speed: 20 rpm Head rotation speed: 20 rpm Polishing pad: Fujibo Ehime Co., Ltd., product name "FP55" Polishing time: 100 seconds Polishing solution temperature: 20℃ Polishing liquid supply rate: 2.0 liters / minute (flow-through type).
[0189] [Main polishing] The polishing compositions according to the respective examples prepared above were used as polishing liquids to polish the silicon wafers obtained through the above-mentioned preliminary polishing under the polishing conditions described below.
[0190] [Polishing conditions] Polishing equipment: Okamoto Machine Tool Works' sheet-fed polishing machine, model "PNX-332B" Polishing load: 15kPa Plate rotation speed: 30 rpm Head rotation speed: 30 rpm Polishing pad: Fujibo Ehime Co., Ltd., product name "POLYPAS27NX" Polishing time: 4 minutes Polishing solution temperature: 20℃ Polishing liquid supply rate: 2.0 liters / minute (flow-through type).
[0191] <LPD-N number measurement> The number of LPD-N particles present on the surface (polished surface) of the silicon wafer obtained by the above polishing was counted using a wafer inspection device manufactured by KLA-Tencor Corporation, product name "SURFSCAN SP2," in the DCO mode of the device.
[0192] <LPD number measurement> The number of LPDs present on the surfaces (polished surfaces) of the silicon wafers obtained by the above polishing was counted using a wafer inspection device manufactured by KLA-Tencor Corporation, product name "SURFSCAN SP2," in the DCO mode of the device.
[0193] The evaluation results of LPD-N and LPD are shown in the following Tables 4 and 5, respectively. The values of LPD-N and LPD in the following Tables 4 and 5 are relative values when the values of LPD-N and LPD in Comparative Examples 1 and 2 are set to 100%, respectively.
[0194] [Table 4]
[0195] [Table 5]
[0196] From the results of Tables 4 and 5, it was confirmed that the polishing composition according to the embodiment has a reduced D90 value. This is believed to be due to the amount of high molecular weight of the raw water-soluble polymer contained in the polishing composition being reduced, and / or the diameter of the molecular chain of the high molecular weight being reduced. In general, the larger the weight molecular weight of a polymer, the easier it is to be adsorbed to abrasive grains, and the adsorbed water-soluble polymer further adsorbs abrasive grains, resulting in coarse particles. In the polishing composition according to the embodiment, the high molecular weight of the raw water-soluble polymer, which may be the cause of the above-mentioned coarse particles, was removed, and therefore the D90 of the polishing composition containing the water-soluble polymer was reduced.
[0197] Furthermore, from the results of Tables 4 and 5 above, it was confirmed that when a polishing composition containing a water-soluble polymer obtained through a collision process was used, the amount of LPD-N and LPD was significantly smaller than when a polishing composition containing a water-soluble polymer that had not been subjected to a collision process was used.
[0198] In addition, as mentioned above, it has been confirmed that the hydroxyethyl cellulose according to the embodiment can suppress the increase of metal impurities.Therefore, it is considered that the polishing composition prepared by using the hydroxyethyl cellulose according to the embodiment or the aqueous solution containing the same can also prevent the increase in the number and size of coarse particles and the amount of metal impurities, and the amount of surface defects caused by them can also be reduced.
Claims
1. A polishing composition comprising an abrasive grain and a water-soluble polymer having a weight average molecular weight (Mw) / number average molecular weight (Mn) ratio of 10 or less, The water-soluble polymer is A step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution; applying pressure to the solutions by colliding them with each other; A water-soluble polymer treated by a method comprising: Satisfy the following [1], Polishing composition; [1] In a differential molecular weight distribution curve of the raw water-soluble polymer, when the value of the vertical axis dw / d(LogM) is 20, the larger of the two values of the horizontal axis LogM is taken as LogM(R), and in a differential molecular weight distribution curve of the water-soluble polymer, when the value of the vertical axis dw / d(LogM) is 20, the larger of the two values of the horizontal axis LogM is taken as LogM(P), the ratio of LogM(P) to LogM(R) is 93% or less.
2. The polishing composition according to claim 1, further satisfying at least one selected from the group consisting of the following [2] and [3]: [2] in the differential molecular weight distribution curve of the raw water-soluble polymer, when the vertical axis dw / d(LogM) is dw / d(LogM(r)) when the horizontal axis LogM value is 4.5, and when the vertical axis dw / d(LogM) is dw / d(LogM(p)) when the horizontal axis LogM value is 4.5 in the differential molecular weight distribution curve of the water-soluble polymer, the ratio of dw / d(LogM(p)) to dw / d(LogM(r)) is within the range of 100±5%; [3] When the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the raw water-soluble polymer is defined as LogM(r_peak) and the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer is defined as LogM(p_peak), the ratio of LogM(p_peak) to LogM(r_peak) is within the range of 100±5%.
3. The weight average molecular weight (Mw) of the raw material water-soluble polymer is 2,000 to 4,000,000.
3. The polishing composition according to claim 1, wherein Mw / Mn of the raw material water-soluble polymer is 95 or less.
4. The polishing composition according to any one of claims 1 to 3, wherein the raw water-soluble polymer is a cellulose derivative, the weight average molecular weight (Mw) of the cellulose derivative is 2,000 or more and 4,000,000 or less, and the Mw / Mn of the cellulose derivative is more than 10 and 95 or less.
5. 5. The polishing composition according to claim 1, wherein the step of applying pressure to the solution is a step of performing a jet mill treatment.
6. A method for producing a polishing composition comprising an abrasive grain and a water-soluble polymer having a weight average molecular weight (Mw) / number average molecular weight (Mn) ratio of 10 or less, comprising the steps of: A step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution; applying pressure to the solutions by colliding them with each other; mixing abrasive particles into the solution under pressure; Including, Satisfy the following [1], Method for producing a polishing composition; [1] In a differential molecular weight distribution curve of the raw water-soluble polymer, when the value of the vertical axis dw / d(LogM) is 20, the larger of the two values of the horizontal axis LogM is taken as LogM(R), and in a differential molecular weight distribution curve of the water-soluble polymer, when the value of the vertical axis dw / d(LogM) is 20, the larger of the two values of the horizontal axis LogM is taken as LogM(P), the ratio of LogM(P) to LogM(R) is 93% or less.
7. The method for producing a polishing composition according to claim 6, further satisfying at least one selected from the group consisting of the following [2] and [3]: [2] in the differential molecular weight distribution curve of the raw water-soluble polymer, when the vertical axis dw / d(LogM) is dw / d(LogM(r)) when the horizontal axis LogM value is 4.5, and when the vertical axis dw / d(LogM) is dw / d(LogM(p)) when the horizontal axis LogM value is 4.5 in the differential molecular weight distribution curve of the water-soluble polymer, the ratio of dw / d(LogM(p)) to dw / d(LogM(r)) is within the range of 100±5%; [3] When the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the raw water-soluble polymer is defined as LogM(r_peak) and the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer is defined as LogM(p_peak), the ratio of LogM(p_peak) to LogM(r_peak) is within the range of 100±5%.
8. 8. The method for producing a polishing composition according to claim 6, wherein the weight average molecular weight (Mw) of the raw water-soluble polymer is 2,000 or more and 4,000,000 or less, and the Mw / Mn of the raw water-soluble polymer is 95 or less.
9. The method for producing a polishing composition according to any one of claims 6 to 8, wherein the raw water-soluble polymer is a cellulose derivative, the weight average molecular weight (Mw) of the cellulose derivative is 2,000 or more and 4,000,000 or less, and the Mw / Mn of the cellulose derivative is more than 10 and 95 or less.
10. The method for producing a polishing composition according to any one of claims 6 to 9, wherein the step of applying pressure to the solution is a step of performing a jet mill treatment.
11. The method for producing a polishing composition according to any one of claims 6 to 10, further comprising the step of filtering the solution after the step of applying pressure to the solution and before the step of mixing abrasive grains into the solution.
12. The method for producing a polishing composition according to any one of claims 6 to 11, further comprising the step of filtering the solution after the step of mixing abrasive grains in the solution.
13. A wetting agent for semiconductors, comprising a water-soluble polymer having a weight average molecular weight (Mw) / number average molecular weight (Mn) ratio of 10 or less, The water-soluble polymer is A step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution; applying pressure to the solutions by colliding them with each other; A water-soluble polymer treated by a method comprising: Satisfy the following [1], Wetting agents for semiconductors; [1] In a differential molecular weight distribution curve of the raw water-soluble polymer, when the value of the vertical axis dw / d(LogM) is 20, the larger of the two values of the horizontal axis LogM is taken as LogM(R), and in a differential molecular weight distribution curve of the water-soluble polymer, when the value of the vertical axis dw / d(LogM) is 20, the larger of the two values of the horizontal axis LogM is taken as LogM(P), the ratio of LogM(P) to LogM(R) is 93% or less.
14. The wetting agent for semiconductors according to claim 13, further satisfying at least one selected from the group consisting of the following [2] and [3]: [2] in the differential molecular weight distribution curve of the raw water-soluble polymer, when the vertical axis dw / d(LogM) is dw / d(LogM(r)) when the horizontal axis LogM value is 4.5, and when the vertical axis dw / d(LogM) is dw / d(LogM(p)) when the horizontal axis LogM value is 4.5 in the differential molecular weight distribution curve of the water-soluble polymer, the ratio of dw / d(LogM(p)) to dw / d(LogM(r)) is within the range of 100±5%; [3] When the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the raw water-soluble polymer is defined as LogM(r_peak) and the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer is defined as LogM(p_peak), the ratio of LogM(p_peak) to LogM(r_peak) is within the range of 100±5%.
15. 15. The wetting agent for semiconductors according to claim 13, wherein the weight average molecular weight (Mw) of the raw water-soluble polymer is 2,000 or more and 4,000,000 or less, and the Mw / Mn of the raw water-soluble polymer is 95 or less.
16. The wetting agent for semiconductors according to any one of claims 13 to 15, wherein the raw water-soluble polymer is a cellulose derivative, the weight average molecular weight (Mw) of the cellulose derivative is 2,000 or more and 4,000,000 or less, and the Mw / Mn of the cellulose derivative is more than 10 and 95 or less.
17. The wetting agent for semiconductor devices according to any one of claims 13 to 16, wherein the step of applying pressure to the solution is a step of performing a jet mill treatment.
18. A method for producing a wetting agent for semiconductors, comprising: A step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution; applying pressure to the solutions by colliding them with each other; mixing other ingredients into the solution under pressure; Including, Satisfy the following [1], Method for producing a wetting agent for semiconductors; [1] In a differential molecular weight distribution curve of the raw water-soluble polymer, when the value of the vertical axis dw / d(LogM) is 20, the larger of the two values of the horizontal axis LogM is taken as LogM(R), and in a differential molecular weight distribution curve of the water-soluble polymer, when the value of the vertical axis dw / d(LogM) is 20, the larger of the two values of the horizontal axis LogM is taken as LogM(P), the ratio of LogM(P) to LogM(R) is 93% or less.
19. The method for producing a wetting agent for a semiconductor according to claim 18, further satisfying at least one selected from the group consisting of the following [2] and [3]: [2] in the differential molecular weight distribution curve of the raw water-soluble polymer, when the vertical axis dw / d(LogM) is dw / d(LogM(r)) when the horizontal axis LogM value is 4.5, and when the vertical axis dw / d(LogM) is dw / d(LogM(p)) when the horizontal axis LogM value is 4.5 in the differential molecular weight distribution curve of the water-soluble polymer, the ratio of dw / d(LogM(p)) to dw / d(LogM(r)) is within the range of 100±5%; [3] When the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the raw water-soluble polymer is defined as LogM(r_peak) and the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer is defined as LogM(p_peak), the ratio of LogM(p_peak) to LogM(r_peak) is within the range of 100±5%.
20. 20. The method for producing a wetting agent for semiconductors according to claim 18 or 19, wherein the weight average molecular weight (Mw) of the raw water-soluble polymer is 2,000 or more and 4,000,000 or less, and the Mw / Mn of the raw water-soluble polymer is 95 or less.
21. The method for producing a semiconductor wetting agent according to any one of claims 18 to 20, wherein the raw water-soluble polymer is a cellulose derivative, the weight average molecular weight (Mw) of the cellulose derivative is 2,000 or more and 4,000,000 or less, and the Mw / Mn of the cellulose derivative is more than 10 and 95 or less.
22. The method for producing a wetting agent for semiconductors according to any one of claims 18 to 21, wherein the step of applying pressure to the solution is a step of performing a jet mill treatment.
23. A method for treating a water-soluble polymer used in the production method according to claim 6, 7, 8, 9, 10, 11, 12, 18, 19, 20, 21 or 22, comprising the steps of: A step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution; applying pressure to the solutions by colliding them with each other; A method for treating a water-soluble polymer comprising the steps of:
24. A step of dissolving a raw material water-soluble polymer in a solvent to prepare a solution; applying pressure to the solutions by colliding them with each other; a water-soluble polymer treated by a method comprising the steps of: Where: The water-soluble polymer is used as a polishing composition and / or a wetting agent for semiconductors, The weight average molecular weight (Mw) / number average molecular weight (Mn) of the water-soluble polymer is 10 or less, The water-soluble polymer satisfies the following [1]: [1] In the differential molecular weight distribution curve of the raw material water-soluble polymer, the vertical axis dw / d (LogM When the larger of the two values of Log M on the horizontal axis when the value of dw / d(Log M) on the vertical axis in the differential molecular weight distribution curve of the water-soluble polymer is 20 is taken as Log M(R), and the larger of the two values of Log M on the horizontal axis when the value of dw / d(Log M) on the vertical axis is 20 in the differential molecular weight distribution curve of the water-soluble polymer is taken as Log M(P), the ratio of Log M(P) to Log M(R) is 93% or less.
25. The water-soluble polymer according to claim 24, which further satisfies at least one of the following conditions [2] and [3]: [2] in the differential molecular weight distribution curve of the raw water-soluble polymer, when the vertical axis dw / d(LogM) is dw / d(LogM(r)) when the horizontal axis LogM value is 4.5, and when the vertical axis dw / d(LogM) is dw / d(LogM(p)) when the horizontal axis LogM value is 4.5 in the differential molecular weight distribution curve of the water-soluble polymer, the ratio of dw / d(LogM(p)) to dw / d(LogM(r)) is within the range of 100±5%; [3] When the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the raw water-soluble polymer is defined as LogM(r_peak) and the LogM at which dw / d(LogM) has a peak in the differential molecular weight distribution curve of the water-soluble polymer is defined as LogM(p_peak), the ratio of LogM(p_peak) to LogM(r_peak) is within the range of 100±5%.
26. 26. The water-soluble polymer according to claim 24, wherein the weight average molecular weight (Mw) of the raw water-soluble polymer is 2,000 or more and 4,000,000 or less, and the Mw / Mn of the raw water-soluble polymer is 95 or less.
27. The water-soluble polymer according to any one of claims 24 to 26, wherein the raw material water-soluble polymer is a cellulose derivative, the weight average molecular weight (Mw) of the cellulose derivative is 2,000 or more and 4,000,000 or less, and the Mw / Mn of the cellulose derivative is more than 10 and 95 or less.
28. The water-soluble polymer according to any one of claims 24 to 27, wherein the step of applying pressure to the solution is a step of performing a jet mill treatment.
29. A method for polishing a substrate, comprising using the polishing composition according to any one of claims 1 to 5.
30. A method for rinsing a substrate, using the wetting agent for semiconductors according to any one of claims 13 to 17.
31. 30. The method of claim 29, wherein the substrate is a single crystal silicon wafer.
32. 31. The method of claim 30, wherein the substrate is a single crystal silicon wafer.
Citation Information
Patent Citations
Abrasive and production method therefor
JP2004244566A
Polishing composition, polishing composition manufacturing method and semiconductor substrate manufacturing method using polishing composition
JP2014036206A
Polishing composition and manufacturing method for substrate
JP2014049633A
Polishing fluid for metallic film and method for producing semiconductor substrate using the same
WO2003021651A1
Polishing composition and method for producing substrate
WO2014034425A1